Main agent for two-component curable urethane adhesive

JP2025032980APending Publication Date: 2025-03-12SANYO CHEM IND LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024129602
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-28
Filing Date
2024-08-06
Publication Date
2025-03-12

Smart Images

  • Figure 2025032980000001
    Figure 2025032980000001
  • Figure 2025032980000002
    Figure 2025032980000002
  • Figure 2025032980000003
    Figure 2025032980000003
Patent Text Reader

Abstract

To provide a main agent capable of obtaining a two-component curable urethane adhesive which exhibits sufficiently low adhesive strength even without using an additive for imparting light release properties, can secure transparency, has good followability to an adherend and can reduce the generation of chips during machining.SOLUTION: There is provided a main agent for a two-component curable urethane adhesive comprising a urethane prepolymer (P) having a hydroxyl group, wherein the (P) is a urethane prepolymer obtained by reacting a polyol component (A) containing a polyester polyol (a1), a polytetramethylene ether glycol (a2) and a polyoxyalkylene polyol (a3) having a hydroxypropyl group at the molecular terminal with an organic polyisocyanate component (B), the (a1) is a reaction product of a polyol component (X) containing a diol (X1) having an alkyl group and a polycarboxylic acid component (Y) and the (a3) has a degree of unsaturation of 0.003 to 0.009 meg / g.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a base agent for a two-component curing urethane adhesive. [Background technology]

[0002] Optical component sheets are made by laminating an adhesive onto a base material (polyester, polyethylene, polypropylene, glass, etc.), and are used by manufacturers of optical components such as polarizing plates to protect the surfaces of optical components before shipping, and by manufacturers of image display devices such as LCD displays to protect optical components during the manufacturing process of display devices (liquid crystal modules) and to attach optical components to each other.

[0003] Acrylic adhesives are mainly used for these optical member sheets, but urethane adhesives are also used because of their good conformability to the adherend, easy peelability, and excellent transparency (for example, Patent Documents 1, 2, and 3). However, in the urethane adhesive disclosed in Patent Document 1, although the crosslinking points and urethane group concentration are increased by using a large amount of curing agent, the adhesive strength of the adhesive sheet is not sufficiently low, and a large force is required to peel the sheet from the optical member, so that the area to be protected is limited to a small area. In addition, in the urethane adhesive disclosed in Patent Document 2, the easy peeling property of the adhesive sheet is achieved by adding a low molecular weight polyol having a number average molecular weight of 300 or less, but there is a problem that the transparency of the adhesive sheet cannot be ensured due to deterioration of compatibility. Furthermore, in the urethane adhesive disclosed in Patent Document 3, the easy peeling property and transparency of the adhesive sheet are both achieved by using a silicone-based additive. However, since silicone may contaminate the adherend and cause problems, a base agent for a urethane adhesive that has a sufficiently low adhesive strength without using an additive that imparts easy peeling property is required. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2006-182795 A [Patent Document 2] JP 2018-62595 A [Patent Document 3] Patent Publication No. 2022-98051 Summary of the Invention [Problem to be solved by the invention]

[0005] The objective of the present invention is to provide a base agent for a two-component curing urethane adhesive that can be used to produce a two-component curing urethane adhesive that exhibits sufficiently low adhesive strength even without the use of additives that impart easy releasability, that ensures transparency, that conforms well to the adherend, and that reduces the generation of cutting chips during processing. [Means for solving the problem]

[0006] The present inventors have conducted intensive research to solve the above problems, and have arrived at the present invention. That is, the present invention is a two-component curing urethane pressure-sensitive adhesive base material containing a urethane prepolymer (P) having a hydroxyl group, the urethane prepolymer (P) being a urethane prepolymer obtained by reacting a polyol component (A) containing a polyester polyol (a1), a polytetramethylene ether glycol (a2) and a polyoxyalkylene polyol (a3) ​​having a hydroxypropyl group at the molecular end with an organic polyisocyanate component (B), the polyester polyol (a1) being a reaction product of a polyol component (X) containing a diol (x1) having an alkyl group with a polycarboxylic acid component (Y), and the polyoxyalkylene polyol (a3) ​​having a degree of unsaturation of 0.003 to 0.009 meq / g. Effect of the Invention

[0007] Two-component curing urethane adhesives using the main agent for the two-component curing urethane adhesive of the present invention have good conformability to the adherend, reduce the generation of cutting chips during processing, and can produce adhesive sheets that exhibit excellent easy releasability and transparency without the addition of components that impart easy releasability. In the following description, the effect of suppressing the generation of cutting chips during machining may be referred to as "cuttability." DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] The base material for a two-component curing urethane adhesive of the present invention is a base material for a two-component curing urethane adhesive containing a urethane prepolymer (P) having a hydroxyl group, the urethane prepolymer (P) being a urethane prepolymer obtained by reacting a polyol component (A) containing a polyester polyol (a1), a polytetramethylene ether glycol (a2) and a polyoxyalkylene polyol (a3) ​​having a hydroxypropyl group at the molecular terminal with an organic polyisocyanate component (B), the polyester polyol (a1) being a reaction product of a polyol component (X) containing a diol (x1) having an alkyl group with a polycarboxylic acid component (Y), and the polyoxyalkylene polyol (a3) ​​having a degree of unsaturation of 0.003 to 0.009 meq / g.

[0009] In the present invention, the urethane prepolymer (P) is a reaction product of a polyol component (A) containing a polyester polyol (a1), a polytetramethylene ether glycol (a2), and a polyoxyalkylene polyol (a3) ​​having a hydroxypropyl group at the molecular terminal, with an organic polyisocyanate component (B), and has a hydroxyl group.

[0010] In the present invention, the polyol component (A) contains a polyester polyol (a1). When the polyol contains (a1), the appearance (transparency) and easy peelability of the cured product of the two-component curing urethane pressure-sensitive adhesive are excellent. The polyester polyol (a1) is a reaction product of a polyol component (X) containing a diol (x1) having an alkyl group and a polycarboxylic acid component (Y). In the diol (x1) having an alkyl group, the alkyl group includes those having 1 to 6 carbon atoms, and examples thereof include a methyl group, an ethyl group, a propyl group, and a butyl group. Of these, from the viewpoints of the appearance (transparency) and easy releasability of the cured product of the two-component curing urethane pressure-sensitive adhesive, a methyl group or an ethyl group is preferred, and a methyl group is more preferred.

[0011] The diol (x1) having an alkyl group includes those having 3 to 20 carbon atoms, and examples thereof include alkylene glycols having 3 to 10 carbon atoms and having an alkyl group {e.g., 2-methyl-1,3-propanediol, 2-ethyl-1,3-propanediol, 2-ethyl-2-methyl-1,3-propanediol, 3-methyl-1,5-pentanediol, neopentyl glycol, 3-ethyl-1,5-pentanediol, 3-propyl-1,5-pentanediol, 2-methyl-1,8-octanediol, etc.}, alicyclic diols having 6 to 10 carbon atoms and having an alkyl group {e.g., 3-methyl-1,2-cyclopropanedimethanol, 2-methyl-1,4-cyclohexanedimethanol, etc.}, and aromatic ring-containing diols having an alkyl group {e.g., alkylene oxide adducts of bisphenols having an alkyl group (e.g., bisphenol A, bisphenol AP, bisphenol B, bisphenol C, bisphenol E, bisphenol G, etc.)}. As the diol (x1) having an alkyl group, from the viewpoint of the appearance (transparency) of the cured product of the two-component curing type urethane pressure-sensitive adhesive, an alkylene glycol having 3 to 10 carbon atoms and an alkyl group is preferable, and 3-methyl-1,5-pentanediol is more preferable.

[0012] The polyol component (X) may contain a polyol other than the diol (x1) having an alkyl group, and examples of such polyols include a linear diol (x2) having 2 to 10 carbon atoms, a diol (x3) having an alicyclic skeleton having 4 to 50 carbon atoms and no alkyl group, an aromatic ring-containing diol (x4) having 8 to 50 carbon atoms and no alkyl group, and a trivalent or higher polyhydric alcohol (x4) having no alkyl group. Examples of the linear diol (x2) having 2 to 10 carbon atoms include linear alkylene glycols having 2 to 10 carbon atoms (e.g., ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,6-hexanediol, 1,9-nonanediol, etc.), alkylene ether glycols (e.g., diethylene glycol, triethylene glycol, etc.), and the like. Examples of the alicyclic diol (x3) having 6 to 50 carbon atoms and not having an alkyl group include 1,4-cyclohexanedimethanol and ethylene oxide adducts of 1,4-cyclohexanedimethanol (number of moles added: 1 to 10). Examples of the aromatic ring-containing diol (x4) having 8 to 50 carbon atoms and no alkyl group include ethylene oxide adducts of bisphenols (such as bisphenol F and bisphenol S) having no alkyl group. The trihydric or higher polyhydric alcohol (x5) includes those having 3 to 8 carbon atoms, such as glycerin, trimethylolethane, trimethylolpropane, pentaerythritol, sorbitol, sorbitan, and polyglycerin. As the polyol other than the diol (x1) having an alkyl group in the polyol component (X), from the viewpoint of easy peeling property, a linear diol (x2) having 2 to 10 carbon atoms is preferable, a linear alkylene glycol having 2 to 6 carbon atoms is more preferable, and 1,4-butanediol is particularly preferable.

[0013] The weight proportion of the diol (x1) having an alkyl group in the polyol component (X) is preferably 70% by weight or more, and more preferably 90% by weight or more, based on the weight of the polyol component (X), from the viewpoints of the properties of the main agent for the two-component curing urethane adhesive and the cuttability of the cured product of the two-component curing urethane adhesive. The weight proportion of the polyols (total of (x2) to (x4)) other than the diol (x1) having an alkyl group in the polyol component (X) is preferably 30% by weight or less, and more preferably 10% by weight or less, based on the weight of the polyol component (X), from the viewpoints of the properties of the main agent for the two-component curing urethane adhesive and the cuttability of the cured product of the two-component curing urethane adhesive.

[0014] Examples of the polycarboxylic acid component (Y) include aliphatic dicarboxylic acids {alkane dicarboxylic acids (y1) having 4 to 36 carbon atoms, alkenyl succinic acids (y2), alicyclic dicarboxylic acids (y3) having 6 to 40 carbon atoms, alkene dicarboxylic acids (y4) having 4 to 36 carbon atoms}, aromatic dicarboxylic acids (y5) having 8 to 36 carbon atoms, and trivalent or higher polycarboxylic acids (y6). Examples of the alkanedicarboxylic acid (y1) having 4 to 36 carbon atoms include succinic acid, adipic acid, sebacic acid, azelaic acid, dodecanedicarboxylic acid, octadecanedicarboxylic acid, and decylsuccinic acid. Examples of the alkenylsuccinic acid (y2) include dodecenylsuccinic acid, pentadecenylsuccinic acid, and octadecenylsuccinic acid. Examples of the alicyclic dicarboxylic acid (y3) having 6 to 40 carbon atoms include dimer acid (dimerized linoleic acid). Examples of the alkene dicarboxylic acid (y4) having 4 to 36 carbon atoms include maleic acid, fumaric acid, and citraconic acid. Examples of the aromatic dicarboxylic acid (y5) having 8 to 36 carbon atoms include phthalic acid, isophthalic acid, terephthalic acid, and naphthalenedicarboxylic acid. Examples of the trivalent or higher polycarboxylic acid (y6) include aromatic polycarboxylic acids having 9 to 20 carbon atoms (such as trimellitic acid and pyromellitic acid) and aliphatic (including alicyclic) tricarboxylic acids having 6 to 36 carbon atoms (such as hexanetricarboxylic acid and decanetricarboxylic acid). From the viewpoint of the hue of the cured product of the two-component curing urethane adhesive, the polycarboxylic acid component (Y) is preferably an aliphatic (including alicyclic) dicarboxylic acid, more preferably an alkanedicarboxylic acid (y1) having 4 to 36 carbon atoms, and particularly preferably adipic acid.

[0015] The number average molecular weight (hereinafter abbreviated as Mn) of the polyester polyol (a1) is preferably from 300 to 10,000, and more preferably from 500 to 6,000, from the viewpoint of easy releasability.

[0016] In the present invention, Mn can be measured by gel permeation chromatography under the following conditions, for example. Apparatus: "Waters Alliance 2695" [Waters] Column: "Guardcolumn Super HL" (1 column), "TSKgel SuperH2000, TSKgel SuperH3000, TSKgel SuperH4000 (registered trademark) [all manufactured by Tosoh Corporation], each connected with 1 column" Sample solution: 0.25% by weight tetrahydrofuran (hereafter abbreviated as THF) solution Solution injection volume: 10μl Flow rate: 0.6ml / min Measurement temperature: 40℃ Detector: Refractive index detector Reference material: Standard polyethylene glycol

[0017] The hydroxyl value of the polyester polyol (a1) is preferably from 10 to 400 mgKOH / g, and more preferably from 20 to 225 mgKOH / g, from the viewpoint of easy releasability. The hydroxyl value in the present invention can be measured by the method described in JIS K 1557-1.

[0018] In the present invention, the polyol component (A) contains polytetramethylene ether glycol (a2). When the polyol component (A) contains (a2), the appearance (transparency) and easy peelability of the cured product of the two-component curing urethane pressure-sensitive adhesive are excellent. The Mn of the polytetramethylene ether glycol (a2) is preferably from 500 to 10,000, and more preferably from 1,000 to 5,000, from the viewpoint of easy peelability.

[0019] In the present invention, the hydroxyl value of the polytetramethylene ether glycol (a2) is preferably from 10 to 225 mgKOH / g, more preferably from 20 to 115 mgKOH / g, from the viewpoint of easy peelability.

[0020] In the present invention, the polyol component (A) contains a polyoxyalkylene polyol (a3) ​​having a hydroxypropyl group at the molecular end. The degree of unsaturation of (a3) ​​is 0.003 to 0.009 meq / g. When (a3) ​​is contained, the composition has excellent light peelability, conformability to the adherend, and cuttability. The polyoxyalkylene polyol (a3) ​​can be any polyoxyalkylene polyol having a hydroxylpropyl group at the molecular end, but from the viewpoint of easy peelability, it is preferable to use a compound represented by the following general formula (1).

[0021] [ka] [In the general formula (1), X represents an m-valent residue obtained by removing active hydrogen atoms from a compound having m active hydrogen atoms; A represents a phenyl group or an alkylene group having 2 to 12 carbon atoms which may be substituted with a halogen atom; Z represents a propylene group; m represents an integer of 2 to 20; p represents an integer of 0 to 199, and q represents an integer of 1 to 200, satisfying 1≦p+q≦200.]

[0022] X in the general formula (1) is an m-valent residue obtained by removing active hydrogen atoms from a compound having m active hydrogen atoms, and m is preferably an integer of 2 to 20. When m is 20 or less, the viscosity of the polyoxyalkylene polyol (a3) ​​is appropriate, and the viscosity of the mixed liquid of the base agent and the curing agent during application is not too high, which is preferable. Examples of the compound having m active hydrogen atoms constituting the residue X include hydroxyl group-containing compounds, amino group-containing compounds, carboxyl group-containing compounds, and compounds having at least one group selected from hydroxyl groups such as thiol, primary or secondary amino groups, carboxyl groups, and mercapto groups.

[0023] Examples of the hydroxyl group-containing compound include low-molecular-weight polyhydric alcohols having a hydroxyl group equivalent of 160 or less [aliphatic polyhydric alcohols [aliphatic dihydric alcohols having 2 to 20 carbon atoms {alkylene glycols, for example, ethylene glycol, propylene glycol, 1,3-butylene glycol, 1,4-butanediol, 1,6-hexanediol, 3-methylpentanediol, neopentyl glycol, 1,9-nonanediol, etc.}; tri- to octahydric or higher polyhydric alcohols having 3 to 8 carbon atoms {glycols, glycerin, trimethylolpropane, pentaerythritol, sorbitol, xylitol, mannitol, etc.}; their intermolecular or intramolecular dehydration products, for example, dipentaerythritol, polyglycerol (degree of polymerization 2-20) and sorbitan; sugars and their derivatives (glycoxides, etc.), for example, glucose, fructose, sucrose, α-methylglucoside, etc.; (bi)cycloalkylenediols having 6 to 15 carbon atoms {for example, 1,4-dihydroxycyclohexane, 1,4-bis (hydroxymethyl)cyclohexane and 2,2-bis(4,4'-hydroxycyclohexyl)propane, etc.}; aromatic ring-containing polyhydric alcohols having 8 to 15 carbon atoms [m- or p-xylylene glycol and 1,4-bis(hydroxyethyl)benzene, etc.]; castor oil-based polyols (castor oil, partially dehydrated castor oil, partially acylated castor oil, etc.); polymers or oligomers having m hydroxyl groups and Mn of 2,000 or less [polyalkadiene (carbon number 4 to 10) polyols, For example, polybutadiene polyol and its hydrogenated products; (co)polymers of hydroxyalkyl (carbon number 2 to 4) (meth)acrylates; polyvinyl alcohol (saponification degree 60% or more); polyhydric phenols [monocyclic polyhydric phenols (pyrogallol, catechol, hydroquinone, etc.), bisphenols (bisphenol A, bisphenol F, bisphenol S, etc.)]; phosphoric acid compounds (phosphoric acid, phosphorous acid, phosphonic acid, etc.); and mixtures of two or more of these.

[0024] Examples of the amino group-containing compound include primary monoamines [mono(cyclo)alkylamines having 1 to 20 carbon atoms (methylamine, ethylamine, butylamine, octylamine, dodecylamine, cyclohexylamine, etc.), aromatic and aromatic aliphatic monoamines having 6 to 12 carbon atoms (aniline, toluidine, benzylamine, etc.)]; polyamines having two or more active hydrogens [aliphatic diamines having 2 to 12 or more carbon atoms {alkylenediamines, for example, ethylenediamine, propylenediamine, hexamethylenediamine, and mono- or di-alkyl (C1-4) alkylenediamines (dimethylpropylenediamine, etc.)}, alicyclic diamines having 6 to 15 carbon atoms (1,4-diaminocyclohexane, isophoronediamine, 4,4'-diaminocyclohexylmethane, etc.), aromatic diamines having 6 to 15 carbon atoms {m- or p-phenylenediamine, tolylenediamine, diethyltoluenediamine, 4,4'-diaminophenylmethane, 2,2-bis(4,4'-diaminophenyl)propane, etc.}, aromatic aliphatic diamines having 8 to 15 carbon atoms (m- or p-oxygenated diamines, rylenediamine, etc.), heterocyclic polyamines having 4 to 10 carbon atoms {piperazine, aminoalkyl (carbon number 2 to 4) piperazines (e.g. aminoethylpiperazine), aminoalkyl (carbon number 2 to 4) imidazoles, etc.}, polyalkylene polyamines having 2 to 4 carbon atoms in the alkylene group {diethylenetriamine, dipropylenetriamine, triethylenetetramine, polyethyleneimine with Mn of 2,000 or less, and mono-, di-, or tri-alkyl (carbon number 1 to 4) polyalkylene polyamines (e.g. dimethyldipropylenetriamine, etc.)} etc.]; mono- or dialkanolamines having a hydroxyalkyl group with 2 to 4 carbon atoms (monoethanolamine, monoisopropanolamine, diethanolamine, diisopropanolamine, etc.); polymers or oligomers having one or more amino groups and an Mn of 2,000 or less (aminoalkyl (having 2 to 4 carbon atoms) (meth)acrylate (co)polymers and polyether (poly)amines (polyoxypropylene diamine, polyoxypropylene triamine, etc.) etc.); and mixtures of two or more of these.

[0025] Examples of the carboxyl group-containing compound include aliphatic polycarboxylic acids having 2 to 36 carbon atoms (such as succinic acid, glutaric acid, adipic acid, sebacic acid, maleic acid, fumaric acid, and dimerized linoleic acid), aromatic polycarboxylic acids having 8 to 15 carbon atoms (such as phthalic acid, isophthalic acid, terephthalic acid, trimellitic acid, and pyromellitic acid), unsaturated carboxylic acid polymers [such as (meth)acrylic acid (co)polymers having an Mn of 2,000 or less], and mixtures of two or more of these.

[0026] Examples of thiols include divalent to octavalent polythiols having 2 to 6 or more carbon atoms (ethanedithiol, propanedithiol, 1,3- or 1,4-butanedithiol, 1,6-hexanedithiol, and 3-methyl-1,5-pentanedithiol, etc.).

[0027] Among these, from the viewpoint of curability, preferred are hydroxyl group-containing compounds and amino group-containing compounds, and more preferred are aliphatic polyhydric alcohols having a hydroxyl group equivalent of 160 or less and castor oil-based polyols, in particular, propylene glycol, glycerin, pentaerythritol, dipentaerythritol, polyglycerin (degree of polymerization 2 to 10), and castor oil.

[0028] A in the general formula (1) is a phenyl group or an alkylene group having 2 to 12 carbon atoms which may be substituted with a halogen atom, and examples of such alkylene groups include linear or branched alkylene groups having 2 to 12 carbon atoms, cycloalkylene groups having 6 to 10 carbon atoms, and those substituted with a phenyl group, a halophenyl group, or a halogen atom (Cl, Br, etc.).

[0029] Specific examples of A include an ethylene group, a 1,2- or 1,3-propylene group, a 1,2-, 2,3-, 1,3- or 1,4-butylene group, a 1,2-alkylene group having 5 to 12 carbon atoms (such as a 1,2-dodecylene group), a 1,2-cyclohexylene group, a chloropropylene group, a bromopropylene group, a phenylethylene group, and a chlorophenylethylene group.

[0030] (AO) in the general formula (1) is obtained by adding an alkylene oxide (hereinafter abbreviated as AO) to a compound having m active hydrogen atoms constituting the residue X. Examples of AO to be used include ethylene oxide (hereinafter abbreviated as EO), 1,2-propylene oxide (hereinafter abbreviated as PO), 1,3-propylene oxide, 1,2-, 1,3-, 2,3- or 1,4-butylene oxide (hereinafter abbreviated as BO for butylene oxide), α-olefin oxide having 5 to 12 carbon atoms, epihalohydrin (epichlorohydrin, epibromohydrin, etc.), styrene oxide, 1,2-cyclohexene oxide, and a combination of two or more of these. When p (AO) are composed of two or more oxyalkylene groups, the bonding mode may be either block or random. Among these, PO and 1,2-BO are preferred from the viewpoint of flexibility.

[0031] In the general formula (1), Z is a propylene group, p is an integer of 0 to 199, and q is an integer of 1 to 200, which satisfies 1≦p+q≦200.

[0032] The polyoxyalkylene polyol (a3) ​​has a hydroxypropyl group at the end. The presence of a hydroxypropyl group at the end can be confirmed by, for example, 1 This can be done by H-NMR method. The hydroxypropyl group includes a primary hydroxyl group (a hydroxyl group bonded to a primary carbon)-containing group represented by the following chemical formula (2) and a secondary hydroxyl group (a hydroxyl group bonded to a secondary carbon)-containing group represented by the following chemical formula (2'), and the primary hydroxyl group content (hereinafter referred to as the primary hydroxyl group ratio), which is the ratio of the number of primary hydroxyl group-containing groups to the total number of primary hydroxyl group-containing groups and secondary hydroxyl group-containing groups, is preferably 40% or more, more preferably 60% or more. If the primary hydroxyl group ratio is 40% or more, the light peelability tends to be excellent.

[0033] [ka]

[0034] [ka]

[0035] The primary hydroxyl group ratio can be determined by measuring it by the H-NMR method after pretreating (esterifying) the sample in advance. 1 It can be determined by measurement using the H-NMR method.

[0036] 1 The details of the H-NMR method will be described below. <Sample preparation method> Weigh about 30 mg of the measurement sample into an NMR sample tube with a diameter of 5 mm, add about 0.5 ml of a deuterated solvent, and dissolve it. Then, add about 0.1 ml of trifluoroacetic anhydride to make an analysis sample. As the deuterated solvent, for example, a solvent capable of dissolving the sample is appropriately selected from deuterated chloroform, deuterated toluene, deuterated dimethyl sulfoxide, deuterated dimethylformamide, etc. <NMR measurement> Under general conditions 1 Perform H-NMR measurement. <Calculation method of primary hydroxyl group ratio> By the method of pretreatment described above, the hydroxyl group at the end of the polyoxyalkylene polyol reacts with the added trifluoroacetic anhydride to form a trifluoroacetic acid ester. As a result, the signal derived from the methylene group bonded to the primary hydroxyl group is observed around 4.3 ppm, and the signal derived from the methine group bonded to the secondary hydroxyl group is observed around 5.2 ppm. The primary hydroxyl group ratio is calculated by the following formula. Primary hydroxyl group ratio (%) = [x / (x + 2 × y)] × 100 However, x is the integral value of the signal derived from the methylene group bonded to the primary hydroxyl group around 4.3 ppm, and y is the integral value of the signal derived from the methine group bonded to the secondary hydroxyl group around 5.2 ppm.

[0037] The polyoxyalkylene polyol (a3) ​​can be produced, for example, by the method described in JP-A-2000-344881. A preferred example of (a3) ​​is one obtained by ring-opening addition polymerization of PO with an active hydrogen-containing compound (a0) represented by the following general formula (3) in the presence of a tris(pentafluorophenyl)borane catalyst (hereinafter abbreviated as TPB).

[0038] [ka]

[0039] In the general formula (3), X, A and m are the same as those in the general formula (1), and p is 0 or an integer of 1-199.

[0040] Specific examples of (a0) when p is 0 include the same as those exemplified as the compound having m active hydrogen atoms constituting the residue of general formula (1).

[0041] When p is 1 or more, (a0) is a polyol obtained by (co)adding AO to a compound constituting residue X using a conventionally known catalyst (such as an alkali metal hydroxide), and preferred examples thereof include a PO adduct of propylene glycol, a PO adduct of glycerin, a PO adduct of polyglycerin, a 1,2-BO adduct of propylene glycol, a 1,2-BO adduct of glycerin, a 1,2-BO adduct of polyglycerin, a PO / 1,2-BO co-adduct of glycerin (block or random), and the like.

[0042] The amount of TPB used when producing the polyoxyalkylene polyol (a3) ​​by ring-opening addition polymerization of PO to (a0) is not particularly limited, but is preferably 0.00005 to 10 wt %, more preferably 0.0001 to 1 wt %, based on the weight of (a3).

[0043] The number of moles of PO added is 1 to 200 moles, preferably 2 to 100 moles, and more preferably 3 to 30 moles per active hydrogen atom of (a0). The number of moles of all AO (the sum of AO in the first step and PO in the second step) added per active hydrogen atom of the compound constituting the residue X is 1 to 200 moles, and preferably 3 to 100 moles. If the number of moles added exceeds 200 moles, the viscosity of the polyoxyalkylene polyol (a3) ​​increases, and the viscosity of the mixture of the base agent and the curing agent increases when the mixture is applied.

[0044] Therefore, q in the general formula (1) is 1 to 200, preferably 2 to 100, and more preferably 3 to 30. Furthermore, p+q in the general formula (1) is 1 to 200, and preferably 3 to 100.

[0045] The reaction temperature in the ring-opening addition polymerization of PO is preferably 0 to 250° C., more preferably 20 to 180° C. From the viewpoint of controlling the reaction temperature, a method in which PO is added dropwise to a mixture of (a0) and TPB, or a mixture of PO and TPB is added dropwise to (a0) is preferred.

[0046] Since the produced addition polymer contains TPB, it is removed by adsorption using adsorbents such as synthetic silicates (magnesium silicate, aluminum silicate, etc.) and activated clay.

[0047] Specific preferred examples of the polyoxyalkylene polyol (a3) ​​constituting the polyol component (A) in the present invention include a PO adduct of propylene glycol, a PO adduct of polypropylene glycol (with a terminal secondary hydroxyl group), a PO adduct of glycerin, a PO adduct of polyglycerin, a PO adduct of a 1,2-BO adduct of propylene glycol (with a terminal secondary hydroxyl group), a PO adduct of a 1,2-BO adduct of glycerin (with a terminal secondary hydroxyl group), a PO adduct of a 1,2-BO adduct of glycerin (with a terminal secondary hydroxyl group), a PO adduct of a 1,2-BO adduct of polyglycerin (with a terminal secondary hydroxyl group), and a PO adduct of castor oil.

[0048] The Mn of the polyoxyalkylene polyol (a3) ​​is preferably from 500 to 20,000, more preferably from 1,000 to 10,000, and particularly preferably from 2,000 to 6,000, from the viewpoint of the cuttability and easy peelability of the cured product of the two-component curing urethane pressure-sensitive adhesive.

[0049] The hydroxyl value of the polyoxyalkylene polyol (a3) ​​is preferably 5 to 500 mgKOH / g, more preferably 10 to 250 mgKOH / g, and particularly preferably 20 to 150 mgKOH / g, from the viewpoint of the cuttability and easy peelability of the cured product of the two-component curing urethane adhesive.

[0050] The number-average number of functional groups per molecule of the polyoxyalkylene polyol (a3) ​​is preferably 2.1 to 3.0 from the viewpoint of curability.

[0051] The degree of unsaturation of the polyoxyalkylene polyol (a3) ​​in the present invention is from 0.003 to 0.009 meq / g, preferably from 0.004 to 0.008 meq / g, and more preferably from 0.005 to 0.007 meq / g. When the degree of unsaturation is 0.009 meq / g or less, the cohesive strength of the cured film of the urethane adhesive will be high and the cutting properties will be good, and when it is 0.003 meq / g or more, the cured film of the urethane adhesive will be soft and the conformability to the adherend will be good. The degree of unsaturation in the present invention can be measured by the method described in JIS K1557-3.

[0052] The method for adjusting the unsaturation degree of the polyoxyalkylene polyol (a3) ​​is not particularly limited, but the degree of unsaturation can be reduced by subjecting PO to ring-opening addition polymerization of the active hydrogen-containing compound (a0) in the presence of TPB, and then rearranging the allyl group of the allyl group-containing compound produced as a side reaction during the PO addition reaction to a propenyl group in the presence of an alkali, removing the alkali with an adsorbent, and then hydrolyzing the propenyl group in the presence of an acid to convert it to a hydroxyl group.

[0053] The polyoxyalkylene polyol (a3) ​​may be used alone or in combination of two or more. Examples of the combination include combinations of initiators [compounds having m active hydrogen atoms constituting the residue X in the general formula (1)] of different types [for example, those based on polyhydric alcohols (glycerin, etc.) and those based on polyamines (ethylenediamine, etc.)], those with different numbers of functional groups [m in the general formula (1)] [for example, those based on di- to tri-functional compounds (ethylene glycol, glycerin, etc.) and those based on tetra- to octa-functional compounds (pentaerythritol, sorbitol, sucrose, etc.)], and those with different hydroxyl values ​​or AO addition molar numbers [p+q in the general formula (1)] [those with hydroxyl values ​​of 400 mgKOH / g or more (for example, 450 to 700 mgKOH / g) and those with hydroxyl values ​​less than 400 mgKOH / g (for example, 30 to 300 mgKOH / g)].

[0054] In the present invention, the polyol component (A) constituting the urethane prepolymer (P) may contain, in addition to the polyester polyol (a1), the polytetramethylene ether glycol (a2), and the polyoxyalkylene polyol (a3) ​​having a hydroxypropyl group at the molecular terminal, another polyol (a4). Examples of the other polyols (a4) include hydroxyl group-containing compounds (a41), polyether polyols (a42) which are AO adducts of the hydroxyl group-containing compounds and are other than (a2) and (a3), polyether polyols (a43) which are AO adducts of the amino group-containing compounds and are other than (a3), and polyester polyols (a44) other than (a1).

[0055] Examples of the hydroxyl group-containing compound (a41) include the hydroxyl group-containing compounds exemplified as the compound having m active hydrogen atoms constituting the residue X in the above general formula (1).

[0056] Examples of the polyether polyol (a42) include polyethylene glycol, poly-3-methyltetramethylene ether glycol, copolymerized polyoxyalkylene diols [EO / PO copolymerized diols not having hydroxypropyl groups at their terminals, THF / EO copolymerized diols, THF / 3-methyltetrahydrofuran copolymerized diols, and the like (weight ratios, for example, of 10 / 90 to 90 / 10)] and AO adducts of bisphenol-based compounds not having hydroxypropyl groups at their terminals; trifunctional or higher polyether polyols not having hydroxypropyl groups at their terminals, for example, AO adducts of trivalent or higher polyhydric alcohols [AO adducts of glycerin and AO adducts of trimethylolpropane, and the like]; and those obtained by coupling one or more of these with methylene dichloride.

[0057] Examples of the polyether polyol (a43) include AO adducts of N,N,N',N'-tetrakis(2-hydroxypropyl)-ethylenediamine, N,N,N',N'',N''-pentakis(2-hydroxypropyl)-diethylenetriamine, triethanolamine, and N,N-dimethylpropylenediamine, AO adducts of N,N-dimethyldipropylenetriamine (disclosed in JP-A-11-335436), and AO adducts of N-aminoalkylimidazole (disclosed in JP-A-11-322881).

[0058] Examples of the polyester polyol (a44) include castor oil fatty acid ester polyols (e.g., castor oil, partially dehydrated castor oil, and castor oil fatty acid esters); poly(n=2 to 3 or more) carboxylic acids [aliphatic saturated or unsaturated polycarboxylic acids (having 2 to 40 carbon atoms, e.g., oxalic acid, adipic acid, azelaic acid, dodecanoic acid, maleic acid, fumaric acid, itaconic acid, and dimerized linoleic acid), aromatic ring-containing polycarboxylic acids (having 8 to 15 carbon atoms, e.g., phthalic acid, isophthalic acid, terephthalic acid, and 2,6-naphthalenedicarboxylic acid), and alicyclic ring-containing polycarboxylic acids (having 7 to 15 carbon atoms, e.g., 1,3-pentanedicarboxylic acid, and 1,4-hexanedicarboxylic acid)] and polyols [e.g., dihydric or higher polyhydric alcohols not having an alkyl group (the above (x2) , (x3) and (x4), etc.), (a2) and (a3), etc.); polylactone polyols [for example, polyols (e.g., polycaprolactone polyols) obtained by addition polymerization of one or a mixture of two or more of the above-mentioned hydroxyl group-containing compounds (divalent to trivalent) as an initiator with (substituted) caprolactone (having 6 to 10 carbon atoms, e.g., ε-caprolactone, α-methyl-ε-caprolactone, and ε-methyl-ε-caprolactone) in the presence of a catalyst (an organometallic compound, a metal chelate compound, a fatty acid metal acyl compound, etc.)]; polyether ester polyols obtained by addition polymerization of AO (EO, PO, etc.) to polyesters having carboxyl groups and / or hydroxyl groups at their terminals; polycarbonate polyols; and the like.

[0059] Among the other polyols (a4), from the viewpoint of the hue of the cured product of the two-component curing urethane adhesive, polyols not containing an aromatic ring are preferred, and polyether polyols (a42) are more preferred.

[0060] The Mn of the other polyol (a4) is preferably from 60 to 10,000, and more preferably from 200 to 5,000, from the viewpoint of easy peelability.

[0061] The hydroxyl value of the other polyol (a4) is preferably from 10 to 1,500 mgKOH / g, and more preferably from 20 to 500 mgKOH / g, from the viewpoint of easy peelability.

[0062] The number average functionality of the other polyol (a4) is preferably 2 to 5, more preferably 2 to 4, and particularly preferably 2 to 3, from the viewpoint of curability.

[0063] In the present invention, each of the components (a1) to (a3) ​​in the polyol component (A) and the optional (a4) may be used alone or in combination of two or more kinds.

[0064] In the present invention, the weight proportion of the polyester polyol (a1) in the polyol component (A) constituting the urethane prepolymer (P) is, from the viewpoints of the appearance (transparency) and easy peelability of the cured product of the two-component curing urethane pressure-sensitive adhesive, preferably 1 to 20 wt %, more preferably 2 to 10 wt %, and particularly preferably 3 to 8 wt %, based on the weight of the polyol component (A). In the present invention, the weight proportion of polytetramethylene ether glycol (a2) in the polyol component (A) constituting the urethane prepolymer (P) is, from the viewpoints of the appearance (transparency) and easy peelability of the cured product of the two-component curing urethane pressure-sensitive adhesive, preferably 30 to 60% by weight, more preferably 35 to 55% by weight, and particularly preferably 40 to 50% by weight, based on the weight of the polyol component (A). In the present invention, the weight proportion of the polyoxyalkylene polyol (a3) ​​in the polyol component (A) constituting the urethane prepolymer (P) is, from the viewpoints of easy releasability, conformability to an adherend, and cuttability, preferably from 30 to 65% by weight, more preferably from 35 to 60% by weight, and particularly preferably from 40 to 55% by weight, based on the weight of the polyol component (A). In the present invention, the weight ratio (a3 / a2) of the polyoxyalkylene polyol (a3) ​​to the polytetramethylene ether glycol (a2) in the polyol component (A) constituting the urethane prepolymer (P) is preferably 0.3 to 2.4, more preferably 0.5 to 1.5, from the viewpoints of the properties, easy releasability and cuttability of the main agent for the two-component curing urethane adhesive. In the present invention, the weight proportion of the other polyol (a4) in the polyol component (A) constituting the urethane prepolymer (P) is preferably 20 wt % or less, more preferably 10 wt % or less, and particularly preferably 5 wt % or less, based on the weight of the polyol component (A), from the viewpoints of the appearance (transparency), easy peelability and cuttability of the cured product of the two-component curing urethane adhesive.

[0065] Examples of the organic polyisocyanate component (B) constituting the urethane prepolymer (P) include linear aliphatic polyisocyanates (b1) having 4 to 22 carbon atoms and having 2 to 3 or more isocyanate groups, alicyclic polyisocyanates (b2) having 8 to 18 carbon atoms, aromatic polyisocyanates (b3) having 8 to 26 carbon atoms, araliphatic polyisocyanates (b4) having 10 to 18 carbon atoms, and modified products (b5) of these polyisocyanates. The organic polyisocyanate component (B) may be used alone or in combination of two or more kinds.

[0066] Examples of the chain aliphatic polyisocyanate (b1) having 4 to 22 carbon atoms include ethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate (hereinafter abbreviated as HDI), dodecamethylene diisocyanate, 1,6,11-undecane triisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, lysine diisocyanate, 2,6-diisocyanatomethyl caproate, bis(2-isocyanatoethyl) fumarate, bis(2-isocyanatoethyl) carbonate, and 2-isocyanatoethyl-2,6-diisocyanatohexanoate.

[0067] Examples of the alicyclic polyisocyanate (b2) having 8 to 18 carbon atoms include isophorone diisocyanate (hereinafter abbreviated as IPDI), 4,4'-dicyclohexylmethane diisocyanate, cyclohexylene diisocyanate, methylcyclohexylene diisocyanate, bis(2-isocyanatoethyl)-4-cyclohexene-1,2-dicarboxylate, and 2,5- or 2,6-norbornane diisocyanate.

[0068] Examples of the aromatic polyisocyanate (b3) having 8 to 26 carbon atoms include 1,3- or 1,4-phenylene diisocyanate, 2,4- or 2,6-tolylene diisocyanate (hereinafter abbreviated as TDI), crude TDI, 4,4'- or 2,4'-diphenylmethane diisocyanate (hereinafter abbreviated as MDI), crude MDI, polyaryl polyisocyanate, 4,4'-diisocyanatobiphenyl, 3,3'-dimethyl-4,4'-diisocyanatobiphenyl, 3,3'-dimethyl-4,4'-diisocyanatodiphenylmethane, 1,5-naphthylene diisocyanate, 4,4',4''-triphenylmethane triisocyanate, and m- or p-isocyanatophenylsulfonyl isocyanate.

[0069] Examples of the aralkyl polyisocyanate (b4) having 10 to 18 carbon atoms include m- or p-xylylene diisocyanate and α,α,α',α'-tetramethylxylylene diisocyanate.

[0070] Examples of the modified polyisocyanates (b5) of (b1) to (b4) include modified polyisocyanates (such as modified ones containing a urethane group, a carbodiimide group, an allophanate group, a urea group, a biuret group, a uretdione group, a uretoimine group, an isocyanurate group or an oxazolidone group; those having a free isocyanate group content of preferably 8 to 33% by weight, more preferably 10 to 30% by weight, particularly preferably 12 to 29% by weight), such as modified MDI (such as urethane-modified MDI, carbodiimide-modified MDI and trihydrocarbyl phosphate-modified MDI), urethane-modified TDI, biuret-modified HDI, isocyanurate-modified HDI and isocyanurate-modified IPDI.

[0071] Of these organic polyisocyanate components (B), from the viewpoint of the hue of the cured product of the two-component curing urethane adhesive, preferred are the chain aliphatic polyisocyanates (b1) having 4 to 22 carbon atoms and the alicyclic polyisocyanates (b2) having 8 to 18 carbon atoms, and more preferred are HDI and IPDI.

[0072] The urethane prepolymer (P) constituting the base of the two-component curing urethane pressure-sensitive adhesive of the present invention can be obtained by reacting the polyol component (A) with the organic polyisocyanate component (B) by a conventional method.

[0073] The urethane prepolymer (P) of the present invention can be produced by known urethane production methods, such as a method of reacting a polyol component (A) with an organic polyisocyanate component (B) in the presence or absence of a solvent (toluene, xylene, ethyl acetate, butyl acetate, dimethylformamide, acetone, methyl ethyl ketone, THF, etc.). By adjusting the ratio of the number of moles of active hydrogen-containing groups in (A) to the number of moles of isocyanate in (B), a prepolymer having a hydroxyl group at its terminal or a prepolymer having an isocyanate group at its terminal can be produced.

[0074] For the reaction, a known reaction apparatus (such as a mixing tank equipped with a stirrer or a static mixer) can be used. The reaction temperature is preferably 10 to 160°C, more preferably 25 to 120°C, from the viewpoints of reactivity and suppression of thermal degradation. From the viewpoint of stability, it is preferable to replace the gas phase with nitrogen.

[0075] When the polyol component (A) is reacted with the organic polyisocyanate component (B), the ratio of the number of moles of isocyanate groups in (B) to the number of moles of active hydrogen-containing groups in (A) (number of moles of isocyanate groups / number of moles of active hydrogen-containing groups) is 0.5 to 0.99, preferably 0.55 to 0.95, and more preferably 0.6 to 0.9, from the viewpoint of the strength and adhesive power of the cured product of the resulting adhesive.

[0076] In the present invention, the urethane prepolymer (P) has a hydroxyl group. The hydroxyl value of the urethane prepolymer (P) is preferably 8 to 20 mgKOH / g, more preferably 10 to 17 mgKOH / g, and particularly preferably 12 to 14 mgKOH / g, from the viewpoints of the appearance, cuttability, and easy peelability of the cured product of the two-component curing urethane adhesive.

[0077] The weight proportion of the ester group in the urethane prepolymer (P) is preferably from 0.3 to 10% by weight, more preferably from 1 to 7% by weight, and particularly preferably from 2 to 5% by weight, from the viewpoint of easy releasability. The weight ratio of the ester group in the urethane prepolymer (P) means the weight ratio of the portion corresponding to the ester group (-CO-O-) to the weight of the urethane prepolymer (P), and does not include "-CO-O-" in the urethane bond (-NH-CO-O-). The weight ratio of the ester group is calculated by the following formula. Weight percentage of ester groups in urethane prepolymer (P) [% by weight] = (total weight [g] of the portion corresponding to ester groups in urethane prepolymer (P) / weight [g] of urethane prepolymer (P)) x 100 The total weight of the portions corresponding to the ester groups in the urethane prepolymer (P) can be calculated, for example, by determining the composition of the monomers constituting the urethane prepolymer (P) and the amount of ester groups by NMR or the like, or by calculating from the composition and weight ratio of the raw materials used in the production of the urethane prepolymer (P).

[0078] The concentration of urethane groups in the urethane prepolymer (P) is preferably from 0.5 to 8% by weight, more preferably from 1 to 5% by weight, and particularly preferably from 2 to 3% by weight, from the viewpoint of easy releasability.

[0079] From the viewpoint of the hue of the cured product of the two-component curing urethane adhesive, the aromatic ring concentration in the urethane prepolymer (P) is preferably 5 wt % or less, more preferably 3 wt % or less, and particularly preferably 2 wt % or less. The aromatic ring concentration in the urethane prepolymer (P) means the weight ratio of the portion corresponding to the carbon atoms constituting the aromatic ring to the weight of the urethane prepolymer (P), and is calculated by the following formula. Concentration of aromatic rings in urethane prepolymer (P) [wt %] = (total weight [g] of the parts corresponding to the carbon atoms constituting the aromatic rings in urethane prepolymer (P) / weight [g] of urethane prepolymer (P)) x 100 The total weight of the portions corresponding to the carbon atoms constituting the aromatic rings in the urethane prepolymer (P) can be calculated, for example, by determining the composition of the monomers constituting the urethane prepolymer (P) and the amount of carbon atoms constituting the aromatic rings by NMR or the like, or by calculating from the composition and weight ratio of the raw materials used in the production of the urethane prepolymer (P).

[0080] The weight average molecular weight (hereinafter sometimes abbreviated as Mw) of the urethane prepolymer (P) is preferably from 10,000 to 300,000, and more preferably from 30,000 to 200,000, from the viewpoints of easy releasability, transparency and cuttability. In the present invention, Mw can be measured by gel permeation chromatography under the following conditions, for example. Equipment: "HLC-8120GPC" [Tosoh Corporation] Column: Guardcolumn H XL -H" (1 bottle), "TSKgel GMH XL (Registered Trademark)" (2 bottles) [Both manufactured by Tosoh Corporation] Sample solution: 0.25% by weight in THF solution Solution injection volume: 100μl Flow rate: 1ml / min Measurement temperature: 40℃ Detector: Refractive index detector Reference material: Standard polystyrene

[0081] The base material for the two-component curing urethane adhesive of the present invention contains the urethane prepolymer (P) and may contain a bismuth compound. The bismuth compound may be contained as a catalyst during the production of the urethane prepolymer (P). Examples of the bismuth compound include organic bismuth compounds {e.g., bismuth-based catalysts used as urethanization catalysts [salts of bismuth and monocarboxylic acids having 1 to 12 carbon atoms, bismuth alkoxides, and chelate compounds of bismuth and β-diketones such as acetylacetone]} and inorganic bismuth compounds. Among these, from the viewpoint of controlling the reaction of the urethane prepolymer (P), organic bismuth compounds are preferred, and salts of bismuth and monocarboxylic acids having 1 to 12 carbon atoms are more preferred.

[0082] The base agent for the two-component curing urethane adhesive of the present invention may contain, in addition to the urethane prepolymer (P) and the bismuth compound, by-products produced during the production of each constituent monomer, by-products produced during the production of the urethane prepolymer (P), a solvent, etc.

[0083] From the viewpoint of the properties and transparency of the two-component curing urethane adhesive base, the content of the urethane prepolymer (P) in the two-component curing urethane adhesive base is preferably 20% by weight or more, and more preferably 30 to 80% by weight, based on the weight of the two-component curing urethane adhesive base. From the viewpoints of the properties and easy peelability of the two-component curing urethane adhesive base agent, the content of the bismuth compound in the two-component curing urethane adhesive base agent is preferably 10 to 1,000 ppm, and more preferably 50 to 500 ppm, based on the weight of the two-component curing urethane adhesive base agent. From the viewpoint of the properties of the two-component curing urethane adhesive base, the content of the solvent in the two-component curing urethane adhesive base is preferably 20% by weight or more, and more preferably 20 to 70% by weight, based on the weight of the two-component curing urethane adhesive base.

[0084] The two-component curing urethane adhesive base agent of the present invention is used as a two-component curing urethane adhesive together with a crosslinking agent (C) having an isocyanate group.

[0085] Examples of the crosslinking agent (C) include the organic polyisocyanates exemplified as the organic polyisocyanate component (B), and compounds which are reaction products of the polyols (a1) to (a4) exemplified as the main agent for the two-component curing type urethane adhesive and the organic polyisocyanate component (B) and have an isocyanate group at a terminal.

[0086] From the viewpoint of curability, the number average functionality of the crosslinking agent (C) is preferably 2 or more, more preferably 2-6, and particularly preferably 3-5.

[0087] When producing the urethane prepolymer (P), the two-component curing urethane adhesive, and the adhesive sheet using the same in the present invention, a urethane-forming catalyst can be used depending on the application and the required degree of curing property. The urethane-forming catalyst may be used alone or in combination of two or more kinds.

[0088] Examples of the urethanization catalyst include metal catalysts and amine catalysts. Examples of the metal catalyst include zinc-based catalysts [salts of zinc and monocarboxylic acids having 1 to 12 carbon atoms, bismuth alkoxides, and chelate compounds of bismuth and β-diketones such as acetylacetone], tin-based catalysts [trimethyltin laurate, trimethyltin hydroxide, dimethyltin dilaurate, dibutyltin diacetate, dibutyltin dilaurate (dibutyltin dilaurate), stannous octoate, and dibutyltin maleate], lead-based catalysts [lead oleate, lead 2-ethylhexanoate, lead naphthenate, and lead octenate], and bismuth-based catalysts [bismuth and monocarboxylic acids having 1 to 12 carbon atoms]. Examples of suitable catalysts include salts of carboxylic acids, bismuth alkoxides, and chelate compounds of bismuth with β-diketones such as acetylacetone, titanium-based catalysts [isopropoxytri-N-ethylaminoethyl aminato titanium, tetrabutyl titanate, and tetraisopropoxybisdioctylphosphite titanium, etc.], iron-based catalysts [iron carboxylate compounds (iron lactate, iron ricinoleate, etc.), ferrocene-based compounds (ferrocene, acetylferrocene, etc.), and iron phthalocyanine, etc.], and other metal catalysts [metal salts of naphthenic acids such as cobalt naphthenate, and phenylmercury propionate, etc.].

[0089] Examples of the amine catalyst include triethylenediamine, tetramethylethylenediamine, diazabicycloalkenes (1,8-diazabicyclo[5,4,0]undecene-7 [DBU (manufactured by San-Apro Ltd., (registered trademark)], etc.), dialkyl (carbon number 1 to 3) aminoalkyl (carbon number 2 to 4) amines (dimethylaminoethylamine, dimethylaminopropylamine, diethylaminopropylamine, dipropylaminopropylamine, etc.), heterocyclic aminoalkyl (carbon number 2 to 6) amines (2-(1-aziridinyl)ethylamine, 4-(1-piperidinyl)-2-hexylamine, etc.), and N-methyl and N-ethylmorpholine.

[0090] Among these, diazabicycloalkenes, zinc-based catalysts, bismuth-based catalysts and tin-based catalysts are preferred, and DBU (registered trademark), salts of zinc and monocarboxylic acids having 1 to 12 carbon atoms, salts of bismuth and monocarboxylic acids having 1 to 12 carbon atoms and dibutyltin dilaurate are particularly preferred.

[0091] The amount of the urethanization catalyst used varies depending on the application, but when high speed curing is required, it is preferably 10,000 ppm or less, more preferably 1 to 5,000 ppm, and particularly preferably 10 to 3,000 ppm based on the weight of the two-component curing urethane adhesive. The urethanization catalyst may be used alone or in combination of two or more kinds.

[0092] The two-component curing urethane adhesive using the main agent for the two-component curing urethane adhesive of the present invention may further contain additives such as the above-mentioned solvent, antioxidant, UV absorber, plasticizer, tackifier, filler, pigment, antistatic agent, antigelling agent (urethanization retarder), etc., within a range that does not impair the effects of the present invention. The additives may be added to either the main agent for the two-component curing urethane adhesive of the present invention or the curing agent, or may be added when the main agent for the two-component curing urethane adhesive of the present invention and the curing agent are mixed, but it is preferable to add the additives in advance to the main agent for the two-component curing urethane adhesive of the present invention.

[0093] Examples of the antioxidant include hindered phenol compounds (triethylene glycol-bis[3-(3-t-butyl-5-methyl-4-hydroxyphenyl)propionate], pentaerythrityl-tetrakis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], 2,2-thio-diethylenebis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], etc.) and phosphorous acid ester compounds (tris(2,4-di-t-butylphenyl)phosphite, 2,2-methylenebis(4,6-di-t-butylphenyl)octylphosphite, bis(2,6-di-t-butylphenyl)pentaerythritol-diphosphite, tetrakis(2,4-di-t-butylphenyl)4,4'-biphenylene-diphosphonite, etc.)). These antioxidants may be used alone or in combination of two or more. The amount of the antioxidant used is preferably 5% by weight or less, and more preferably 0.05 to 1% by weight, based on the weight of the two-component curing urethane adhesive, from the viewpoints of antioxidant effect and adhesive strength.

[0094] Examples of ultraviolet absorbers include salicylic acid derivatives (phenyl salicylate, p-octylphenyl salicylate, p-tert-butylphenyl salicylate, etc.), benzophenone compounds [2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2,2'-dihydroxy-4-methoxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxy-5-sulfobenzophenone, 2-hydroxy-4-methoxy-2'-carboxybenzophenone, 2-Hydroxy-4-methoxy-5-sulfobenzophenone trihydrate, 2-hydroxy-4-n-octoxybenzophenone, 2-hydroxy-4-octadecyloxybenzophenone, 2,2',4,4'-tetrahydroxybenzophenone, 4-dodecyloxy-2-hydroxybenzophenone, 2-hydroxy-4-(2-hydroxy-3-methacryloxy)propoxybenzophenone, bis(2-methoxy-4-hydroxy-5-benzoylphenyl)methane, etc.], benzotriazole compounds {2-(2'-hydroxy-5' -methyl-phenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-t-butyl-phenyl)benzotriazole, 2-(2'-hydroxy-3'-t-butyl-5'-methyl-phenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3',5'-di-t-butyl-phenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-4'-n-octoxyphenyl)benzotriazole, 2-(2'-hydroxy-5'-t-butylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-t-butyl-phenyl)benzotriazole ',5'-di-t-amylphenyl)benzotriazole, 2-[2'-hydroxy-3'-(3'',4'',5'',6''-tetrahydrophthalimidomethyl)-5'-methylphenyl]benzotriazole, 2,2-methylenebis[4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol], etc.}, cyanoacrylate compounds (2-ethylhexyl-2-cyano-3,3'-diphenylacrylate, ethyl-2-cyano-3,3'-diphenylacrylate, etc.). The ultraviolet absorbents may be used alone or in combination of two or more.The amount of the ultraviolet absorbing agent used is preferably 5% by weight or less, more preferably 0.1 to 1% by weight, based on the weight of the two-component curing urethane adhesive, from the viewpoints of ultraviolet absorbing effect and adhesive strength.

[0095] Plasticizers include hydrocarbons [process oil, liquid polybutadiene, liquid polyisobutylene, liquid polyisoprene, liquid paraffin, chlorinated paraffin, paraffin wax, copolymers (weight ratio 99.9 / 0.1-0.1 / 99.9) of ethylene and α-olefins (carbon number 3-20), oligomers (Mw 5,000-100,000), copolymers of propylene and α-olefins (carbon number 4-20) excluding ethylene ( Weight ratio 99.9 / 0.1~0.1 / 99.9) oligomer (Mw5,000~100,000)]; chlorinated paraffin; ester [phthalic acid ester [diethyl phthalate (DEP), dibutyl phthalate (DBP), di-2-ethylhexyl phthalate (DOP), didecyl phthalate, dilauryl phthalate, distearyl phthalate, diisononyl phthalate, etc.], adipic acid ester [di(2-ethylhexyl ) adipate (DOA), dioctyl adipate, etc.] and sebacic acid esters (dioctyl sebacate, etc.); animal and vegetable oils and fats (linoleic acid, linolenic acid, etc.); and hydrogenated products of those having unsaturated double bonds that can be hydrogenated; fatty acid esters (butyl stearate, 2-ethylhexyl palmitate, 2-ethylhexyl stearate, behenic acid monoglyceride, 2-ethylhexanoate cetyl, palmitate isopropyl, isostearate cholesteryl, coconut fatty acid methyl, methyl laurate, methyl oleate, methyl stearate, isopropyl myristate, octyldodecyl myristate, myristyl myristate, stearyl stearate, 2-ethylhexyl stearate, isotridecyl stearate, 2-ethylhexanoic acid triglyceride, butyl laurate, octyl oleate), etc. Plasticizers may be used alone or in combination of two or more. The amount of plasticizer used is preferably 100% by weight or less, more preferably 1 to 50% by weight, particularly preferably 3 to 40% by weight, particularly preferably 5 to 35% by weight, and most preferably 10 to 30% by weight, based on the weight of the two-component curing urethane adhesive, from the viewpoint of the cohesive strength of the adhesive.

[0096] Examples of tackifiers include terpene resins, terpene phenol resins, phenol resins, aromatic hydrocarbon modified terpene resins, rosin resins, modified rosin resins, synthetic petroleum resins (aliphatic, aromatic or alicyclic synthetic petroleum resins, etc.), coumarone-indene resins, xylene resins, styrene-based resins, dicyclopentadiene resins, and hydrogenated products of those having unsaturated double bonds that can be hydrogenated, etc. One type of tackifier may be used alone, or two or more types may be used in combination. Among these, from the viewpoint of adhesive strength, those having polarity are preferred, and rosin resin, phenol resin, terpene phenol resin, xylene resin and hydrogenated products thereof are more preferred, and terpene phenol resin and hydrogenated products thereof are particularly preferred. The amount of the tackifier used is preferably 100% by weight or less, more preferably 1 to 50% by weight, particularly preferably 3 to 40% by weight, particularly preferably 5 to 35% by weight, and most preferably 10 to 30% by weight, based on the weight of the two-component curing urethane adhesive, from the viewpoint of adhesive strength and heat resistance.

[0097] Examples of the filler include carbonates (magnesium carbonate, calcium carbonate, etc.), sulfates (aluminum sulfate, calcium sulfate, barium sulfate, etc.), sulfites (calcium sulfite, etc.), molybdenum disulfide, silicates (aluminum silicate, calcium silicate, etc.), diatomaceous earth, silica powder, talc, silica, zeolite, etc. The fillers are preferably fine particles having a volume average particle size of about 0.01 to 5 μm, and one type may be used alone, or two or more types may be used in combination. The amount of the filler used is preferably 250% by weight or less, more preferably 0.5 to 100% by weight, based on the weight of the two-component curing urethane adhesive, from the viewpoint of the cohesive strength of the adhesive.

[0098] Examples of pigments include inorganic pigments (alumina white, graphite, titanium oxide, ultrafine titanium oxide, zinc oxide, black iron oxide, micaceous iron oxide, white lead, white carbon, molybdenum white, carbon black, litharge, lithopone, baryte, cadmium red, cadmium mercury red, red iron oxide, molybdenum red, red lead, yellow lead, cadmium yellow, barium yellow, strontium yellow, titanium yellow, titanium black, chromium oxide green, cobalt oxide, cobalt green, cobalt chromium green, ultramarine, Prussian blue, cobalt blue, cerulean blue, manganese purple, cobalt purple, etc.), and organic pigments (shellac, insoluble azo pigments, soluble azo pigments, condensed azo pigments, phthalocyanine blue, dye lake, etc.). The above pigments are fine particles having a volume average particle size of preferably about 0.01 to 5 μm, and one type may be used alone or two or more types may be used in combination. The amount of pigment used is preferably 250% by weight or less, more preferably 0.1 to 50% by weight, based on the weight of the two-component curing urethane adhesive, from the viewpoint of the cohesive strength of the adhesive.

[0099] Examples of the antistatic agent include polyether polyols, surfactants, metal-based conductive fillers, carbon black, and quaternary ammonium salts with Mw of less than 5,000.

[0100] An example of the gelling inhibitor (urethanization retarder) is a compound (D) represented by the following general formula (4).

[0101] [ka]

[0102] R in general formula (4) 1 and R 2 each independently represents a hydrocarbon group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, or a heterocyclic group having 3 to 5 carbon atoms.

[0103] The compound (D) has the effect of preventing gelation due to a side reaction during urethane formation, ensuring the usable time during two-component curing, and shortening the curing time during curing. The compound (D) may be used alone or in combination of two or more kinds.

[0104] Specific examples of the compound (D) include 2,4-pentanedione (acetylacetone), 3-methyl-2,4-pentanedione, 2,4-hexanedione, 2,2-dimethyl-3,5-hexanedione, 2,4-heptanedione, 3,5-heptanedione, 2,2,6,6-tetramethyl-3,5-heptanedione, 2,4-octanedione, 2,2,7-trimethyl-3,5-octanedione, 2,4-nonanedione, 3-methyl-2,4-nonanedione, 2-methyl-4,6-nonanedione, 1-phenyl-1,3-butanedione (benzoylacetone), dibenzoylmethane, and 2-furoylbenzoylmethane. β-diketones such as acetone, butyl acetoacetate, methyl propionyl acetate, ethyl propionyl acetate, propyl propionyl acetate, isopropyl propionyl acetate, butyl propionyl acetate, methyl butyryl acetate, ethyl butyryl acetate, propyl butyryl acetate, methyl caproyl acetate, ethyl caproyl acetate, propyl caproyl acetate, and butyl caproyl acetate; dialkyl malonates such as dimethyl malonate, diethyl malonate, methyl ethyl malonate, diisopropyl malonate, and dibutyl malonate.

[0105] The amount of compound (D) used is appropriately selected depending on the desired reaction rate and pot life, but is preferably 0.01 to 5 wt%, more preferably 0.03 to 3 wt%, and particularly preferably 0.05 to 1 wt%, based on the weight of the two-component curing urethane adhesive. If it is less than 0.01 wt%, the effect obtained may be weak, and if it exceeds 5 wt%, the staining property of the adherend due to bleed-out may be deteriorated.

[0106] The NCO / OH ratio (the ratio of the number of moles of isocyanate groups to the number of moles of hydroxyl groups) when mixing the base agent and the curing agent is preferably 0.3 to 2.0, more preferably 0.5 to 1.8, and particularly preferably 0.7 to 1.5, from the viewpoint of the strength and adhesive power of the cured product of the resulting adhesive.

[0107] The uses of the two-component curing urethane adhesive using the two-component curing urethane adhesive base agent of the present invention are not particularly limited, but for example, the base agent and the curing agent can be mixed, and then the mixture can be applied to a base film such as a polyester film or a polyolefin film and cured to obtain an adhesive sheet, which can then be attached to an optical component and used as a surface protection film, etc.

[0108] Examples of optical components to which the two-component curing urethane adhesive and adhesive sheet can be applied include polarizing plates, retardation plates, light diffusion plates, anti-reflection films, electromagnetic wave shielding films, and glass substrates used in liquid crystal displays, organic electroluminescence displays, plasma displays, field emission displays, etc.

[0109] Specific examples of the method for forming the pressure-sensitive adhesive sheet include the following methods. A gravure coater, reverse roll coater, comma coater, spin coater, curtain coater, slot coater, bar coater, comma coater, die coater, knife coater, etc. can be used to coat the substrate film with the two-component curing urethane adhesive. The application amount (solid content) of the adhesive during coating is preferably 0.5 to 300 g / m 2 , more preferably 1 to 200 g / m 2 , particularly preferably 10 to 100 g / m 2 It is.

[0110] The coating temperature of the pressure-sensitive adhesive when applied to a base film is preferably 10 to 160°C, and more preferably 25 to 120°C, from the viewpoints of coatability and suppression of thermal degradation, and the viscosity of the pressure-sensitive adhesive at the coating temperature is preferably 0.01 to 100 Pa s, more preferably 0.02 to 50 Pa s, and particularly preferably 0.03 to 10 Pa s, from the viewpoints of formability (ability to apply thick coating and no appearance defects such as warping or sink marks after curing) and coatability. A typical dry laminator or extrusion laminator is used for lamination. After lamination, the adhesive is cured completely by curing at 10 to 50°C for 20 to 150 hours.

[0111] The cured product of the two-component curing urethane adhesive using the two-component curing urethane adhesive base agent of the present invention is a cured product of the two-component curing urethane adhesive containing the two-component curing urethane adhesive base agent and the curing agent containing the crosslinking agent (C) having an isocyanate group. The storage modulus G' of the cured product of the two-component curing urethane adhesive using the two-component curing urethane adhesive main agent of the present invention is preferably 0.01 to 5 MPa, more preferably 0.02 to 2 MPa, particularly preferably 0.05 to 1 MPa at -30°C, and is preferably 0.005 to 3 MPa, more preferably 0.01 to 1 MPa, particularly preferably 0.02 to 0.5 MPa at 100°C. The ratio of G' at -30°C to G' at 100°C [G' at -30°C / G' at 100°C] is preferably 10 or less, more preferably 8 or less, particularly preferably 5 or less, and most preferably 3 or less. If the ratio of G' at -30°C to 100°C is 10 or less, better adhesive strength can be obtained from low to high temperatures.

[0112] The storage modulus in the present invention is measured by the following method. <Viscoelasticity measurement method> Measuring device: Rheogel-E4000 [UBM Co., Ltd.] Measurement tool: Solid shear Measurement temperature: -30~100℃ Heating rate: 5℃ / min Measurement frequency: 10Hz

[0113] From the viewpoint of adhesive strength to an adherend, the urethane group concentration of the cured product of a two-component curing urethane adhesive using the two-component curing urethane adhesive base agent of the present invention is preferably 0.5 to 20 wt %, more preferably 1 to 10 wt %, and particularly preferably 2 to 5 wt %, based on the total weight of the urethane prepolymer (P) in the base agent and the crosslinking agent (C) in the curing agent. EXAMPLES

[0114] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In the following, "parts" refers to "parts by weight."

[0115] [Production of polyoxyalkylene polyol] <Production Example 1> A stainless steel autoclave equipped with a stirrer, a temperature control device, a heat exchanger as a condensation device, a raw material supply line, and an exhaust line was charged with 38.1 parts of a glycerin PO adduct [Sanyo Chemical Industries, Ltd.'s "Sannyx GP-600 (registered trademark)": hydroxyl value = 280 mg KOH / g] and 1.0 parts of potassium hydroxide, and then stirred at 130 ° C under reduced pressure to dissolve uniformly and dehydrate. Then, the pressure inside the autoclave and the condensation device was reduced to 5 kPa. 361 parts of PO were continuously added to the liquid phase through the raw material supply line while controlling the reaction temperature to be kept at 110 ° C. A refrigerant at -30 ° C was circulated to condense and recover PO in the condensation device. Then, after aging at 130 ° C for 4 hours, 0.7 parts of potassium hydroxide was added, and the mixture was stirred at 130 ° C under reduced pressure to dissolve uniformly and dehydrate. The temperature was then raised and heated at 160°C for 20 hours under a nitrogen atmosphere to rearrange the allyl group of the allyl-containing compound generated by a side reaction during the PO addition reaction to a propenyl group. After cooling to 90°C, 6 parts of synthetic silicate [Kyowa Chemical Industry Co., Ltd.'s "Kyoward 600 (registered trademark)] and 8 parts of water were added and mixed for 60 minutes, and the adsorbent was removed by filtration. Next, 0.02 parts of TPB was charged, stirring was started, and the pressure inside the autoclave and condensation equipment was reduced to 5 kPa. 44.4 parts of PO were continuously added to the liquid phase through the raw material supply line over 12 hours while controlling the reaction temperature to be kept at 75°C. A refrigerant of -30°C was circulated to condense and recover PO in the condensation equipment. After aging for 4 hours at 70°C, 0.2 parts of phosphoric acid and 21 parts of water were added to adjust the pH to 4, and the mixture was heated at 150°C for 5 hours under a nitrogen atmosphere to hydrolyze the propenyl group and convert it to a hydroxyl group. The mixture was cooled to 120°C, and the pressure was kept at 5 kPa while steam was introduced, and water and by-product low boiling point compounds were distilled off under reduced pressure. The mixture was heated to 140°C, and water was distilled off under reduced pressure. The mixture was then cooled to 90°C, and 6 parts of a hydrotalcite-based adsorbent [Kyowa Chemical Industry Co., Ltd.'s "Kyoward 1000 (registered trademark)] was added and mixed for 30 minutes, after which the adsorbent was removed by filtration to obtain polyoxyalkylene polyol (a3-1). The hydroxyl value of (a3-1) was 35.8 mgKOH / g, the viscosity was 1.0 Pa·s / 25°C, the primary content rate was 64%, and the degree of unsaturation was 0.005 meq / g.

[0116] <Production Example 2> In an autoclave similar to that in Production Example 1, 92 parts of a glycerin-PO adduct [Sanyo Chemical Industries, Ltd.'s "Sannyx GP-600 (registered trademark)": hydroxyl value = 280 mg KOH / g] and 1.9 parts of potassium hydroxide were charged, and then the mixture was stirred at 130 ° C under reduced pressure to dissolve uniformly and dehydrated. Then, the pressure in the autoclave and the condensation equipment was reduced to 5 kPa. 520 parts of PO were continuously added to the liquid phase through the raw material supply line while controlling the reaction temperature to be kept at 110 ° C. A refrigerant at -30 ° C was circulated in order to condense and recover PO in the condensation equipment. Then, after aging at 130 ° C for 4 hours, 0.7 parts of potassium hydroxide was added, and the mixture was stirred at 130 ° C under reduced pressure to dissolve uniformly and dehydrated. The temperature was then raised and heated at 160°C for 20 hours under a nitrogen atmosphere to rearrange the allyl group of the allyl-containing compound generated by a side reaction during the PO addition reaction to a propenyl group. After cooling to 90°C, 9 parts of synthetic silicate [Kyowa Chemical Industry Co., Ltd.'s "Kyoward 600 (registered trademark)] and 12 parts of water were added and mixed for 60 minutes, and the adsorbent was removed by filtration. Next, 0.03 parts of TPB was charged, and stirring was started, and the pressure inside the autoclave and condensation equipment was reduced to 5 kPa. 160 parts of PO were continuously added to the liquid phase through the raw material supply line over 12 hours while controlling the reaction temperature to be kept at 75°C. A refrigerant at -30°C was circulated to condense and recover PO in the condensation equipment. After aging for 4 hours at 70°C, 0.4 parts of phosphoric acid and 37 parts of water were added to adjust the pH to 4, and the propenyl group was hydrolyzed and converted to a hydroxyl group by heating at 150°C for 5 hours under a nitrogen atmosphere. The mixture was cooled to 120°C, and the pressure was kept at 5 kPa while steam was introduced, and water and by-product low boiling point compounds were distilled off under reduced pressure. The mixture was heated to 140°C, and water was distilled off under reduced pressure. The mixture was then cooled to 90°C, and 10 parts of a hydrotalcite-based adsorbent [Kyowa Chemical Industry Co., Ltd.'s "Kyoward 1000 (registered trademark)] was added and mixed for 30 minutes, after which the adsorbent was removed by filtration to obtain polyoxyalkylene polyol (a3-2). The hydroxyl value of (a3-2) was 34.2 mgKOH / g, the viscosity was 1.1 Pa·s / 25°C, the primary content rate was 72%, and the degree of unsaturation was 0.004 meq / g.

[0117] <Production Example 3> In an autoclave similar to that in Production Example 1, 38.1 parts of a glycerin-PO adduct [Sanyo Chemical Industries, Ltd.'s "Sannyx GP-600 (registered trademark)": hydroxyl value = 280 mg KOH / g] and 1.0 part of potassium hydroxide were charged, and then the mixture was stirred at 130 ° C under reduced pressure to dissolve uniformly and dehydrated. Then, the pressure in the autoclave and the condensation equipment was reduced to 5 kPa. 361 parts of PO were continuously added to the liquid phase through the raw material supply line while controlling the reaction temperature to be kept at 110 ° C. A refrigerant at -30 ° C was circulated in order to condense and recover PO in the condensation equipment. Then, after aging at 130 ° C for 4 hours, 0.7 parts of potassium hydroxide was added, and the mixture was stirred at 130 ° C under reduced pressure to dissolve uniformly and dehydrated. The temperature was then raised and heated at 160°C for 20 hours under a nitrogen atmosphere to rearrange the allyl group of the allyl-containing compound generated by a side reaction during the PO addition reaction to a propenyl group. After cooling to 90°C, 6 parts of synthetic silicate [Kyowa Chemical Industry Co., Ltd.'s "Kyoward 600 (registered trademark)] and 8 parts of water were added and mixed for 60 minutes, and the adsorbent was removed by filtration. Next, 0.02 parts of TPB was charged, stirring was started, and the pressure inside the autoclave and condensation equipment was reduced to 5 kPa. 12.6 parts of PO were continuously added to the liquid phase through the raw material supply line over 12 hours while controlling the reaction temperature to be kept at 75°C. A refrigerant at -30°C was circulated to condense and recover PO in the condensation equipment. After aging for 4 hours at 70°C, 0.2 parts of phosphoric acid and 21 parts of water were added to adjust the pH to 4, and heated at 150°C for 5 hours under a nitrogen atmosphere to hydrolyze the propenyl group and convert it to a hydroxyl group. The mixture was cooled to 120°C, and the pressure was kept at 5 kPa while steam was introduced, and water and by-product low boiling point compounds were distilled off under reduced pressure. The mixture was heated to 140°C, and water was distilled off under reduced pressure. The mixture was then cooled to 90°C, and 6 parts of a hydrotalcite-based adsorbent [Kyowa Chemical Industry Co., Ltd.'s "Kyoward 1000 (registered trademark)] was added and mixed for 30 minutes, after which the adsorbent was removed by filtration to obtain polyoxyalkylene polyol (a3-3). The hydroxyl value of (a3-3) was 37.1 mgKOH / g, the viscosity was 0.9 Pa·s / 25°C, the primary content rate was 43%, and the degree of unsaturation was 0.007 meq / g.

[0118] <Production Example 4> A stainless steel autoclave equipped with a stirrer, a temperature control device, a heat exchanger as a condensation device, a raw material supply line, and an exhaust line was charged with 38.1 parts of a glycerin PO adduct [Sanyo Chemical Industries, Ltd.'s "Sannyx GP-600 (registered trademark)": hydroxyl value = 280 mg KOH / g] and 1.0 parts of potassium hydroxide, and then stirred at 130 ° C under reduced pressure to dissolve uniformly and dehydrate. Then, the pressure inside the autoclave and the condensation device was reduced to 5 kPa. 361 parts of PO were continuously added to the liquid phase through the raw material supply line while controlling the reaction temperature to be kept at 110 ° C. A refrigerant at -30 ° C was circulated to condense and recover PO in the condensation device. Then, after aging at 130 ° C for 4 hours, 0.7 parts of potassium hydroxide was added, and the mixture was stirred at 130 ° C under reduced pressure to dissolve uniformly and dehydrate. The temperature was then raised and heated at 160°C for 40 hours under a nitrogen atmosphere to rearrange the allyl group of the allyl-containing compound generated by a side reaction during the PO addition reaction to a propenyl group. After cooling to 90°C, 6 parts of synthetic silicate [Kyowa Chemical Industry Co., Ltd.'s "Kyoward 600 (registered trademark)] and 8 parts of water were added and mixed for 60 minutes, and the adsorbent was removed by filtration. Next, 0.02 parts of TPB was charged, stirring was started, and the pressure inside the autoclave and condensation equipment was reduced to 5 kPa. 44.4 parts of PO were continuously added to the liquid phase over 12 hours while controlling the reaction temperature to be kept at 75°C through the raw material supply line. A refrigerant of -30°C was circulated to condense and recover PO in the condensation equipment. After aging for 4 hours at 70°C, 0.2 parts of phosphoric acid and 21 parts of water were added to adjust the pH to 4, and the propenyl group was hydrolyzed and converted to a hydroxyl group by heating at 150°C for 5 hours under a nitrogen atmosphere. The mixture was cooled to 120°C, and the pressure was kept at 5 kPa while steam was introduced, and water and by-product low boiling point compounds were distilled off under reduced pressure. The mixture was heated to 140°C, and water was distilled off under reduced pressure. The mixture was then cooled to 90°C, and 6 parts of a hydrotalcite-based adsorbent [Kyowa Chemical Industry Co., Ltd.'s "Kyoward 1000 (registered trademark)] was added and mixed for 30 minutes, after which the adsorbent was removed by filtration to obtain polyoxyalkylene polyol (a3-4). The hydroxyl value of (a3-4) was 36.2 mgKOH / g, the viscosity was 1.0 Pa·s / 25°C, the primary content rate was 66%, and the degree of unsaturation was 0.001 meq / g.

[0119] <Production Example 5> A stainless steel autoclave equipped with a stirrer, a temperature controller, a heat exchanger as a condenser, a raw material supply line, and an exhaust line was charged with 115.8 parts of a glycerin-PO adduct [Sanyo Chemical Industries, Ltd.'s "Sannyx GP-600 (registered trademark)": hydroxyl value = 280 mg KOH / g] and 1.5 parts of potassium hydroxide, and then stirred at 130 ° C under reduced pressure to dissolve uniformly and dehydrate. Then, the pressure inside the autoclave and the condenser was reduced to 5 kPa. 483 parts of PO were continuously added to the liquid phase through the raw material supply line while controlling the reaction temperature to be kept at 110 ° C. A refrigerant at -30 ° C was circulated to condense and recover PO in the condenser. The mixture was then aged at 130°C for 4 hours and cooled to 90°C, after which 2 parts of synthetic silicate (Kyowa Chemical Industry Co., Ltd.'s "Kyoward 600 (registered trademark)"] and 6 parts of water were added and mixed for 60 minutes, and the adsorbent was removed by filtration to obtain polyoxyalkylene polyol (a3-5). The hydroxyl value of (a3-5) was 56.1 mgKOH / g, the viscosity was 0.5 Pa·s / 25°C, the primary content rate was 2%, and the degree of unsaturation was 0.04 meq / g.

[0120] <Production Example 6> A stainless steel autoclave equipped with a stirrer, a temperature controller, a heat exchanger as a condenser, a raw material supply line, and an exhaust line was charged with 38.3 parts of a glycerin-PO adduct [Sanyo Chemical Industries, Ltd.'s "Sannyx GP-600 (registered trademark)": hydroxyl value = 280 mg KOH / g] and 4.3 parts of potassium hydroxide, and then stirred at 130 ° C under reduced pressure to dissolve uniformly and dehydrate. Then, the pressure inside the autoclave and the condenser was reduced to 5 kPa. 428 parts of PO were continuously added to the liquid phase through the raw material supply line while controlling the reaction temperature to be kept at 110 ° C. A refrigerant at -30 ° C was circulated to condense and recover PO in the condenser. The mixture was then aged at 130°C for 4 hours and cooled to 90°C, after which 3 parts of synthetic silicate (Kyowa Chemical Industry Co., Ltd.'s "Kyoward 600 (registered trademark)"] and 2 parts of water were added and mixed for 60 minutes, and the adsorbent was removed by filtration to obtain polyoxyalkylene polyol (a3-6). The hydroxyl value of (a3-6) was 32.8 mg KOH / g, the viscosity was 0.9 Pa·s / 25°C, the primary content rate was 2%, and the degree of unsaturation was 0.07 meq / g.

[0121] <Production Example 7> A stainless steel autoclave equipped with a stirrer, a temperature controller, a heat exchanger as a condenser, a raw material supply line, and an exhaust line was charged with 30.3 parts of a glycerin PO adduct [Sanyo Chemical Industries, Ltd.'s "Sannyx PP-400 (registered trademark)": hydroxyl value = 280 mg KOH / g] and 1.2 parts of potassium hydroxide, and then stirred at 130 ° C under reduced pressure to dissolve uniformly and dehydrate. Then, the pressure inside the autoclave and the condenser was reduced to 5 kPa. 441 parts of PO was continuously added to the liquid phase through the raw material supply line while controlling the reaction temperature to be kept at 110 ° C. A refrigerant at -30 ° C was circulated to condense and recover PO in the condenser. The mixture was then aged at 130°C for 4 hours and cooled to 90°C, after which 4 parts of synthetic silicate (Kyowa Chemical Industry Co., Ltd.'s "Kyoward 600 (registered trademark)"] and 5 parts of water were added and mixed for 60 minutes, and the adsorbent was removed by filtration to obtain polyoxyalkylene polyol (a3-7). (a3-7) had a hydroxyl value of 27.1 mgKOH / g, a viscosity of 1.0 Pa·s / 25°C, a primary content rate of 2%, and a degree of unsaturation of 0.13 meq / g.

[0122] <Production Example 8> A stainless steel autoclave equipped with a stirrer, a temperature control device, a heat exchanger as a condensation device, a raw material supply line, and an exhaust line was charged with 30.3 parts of a glycerin PO adduct [Sanyo Chemical Industries, Ltd.'s "Sannyx PP-400 (registered trademark)": hydroxyl value = 280 mg KOH / g] and 1.2 parts of potassium hydroxide, and then stirred at 130 ° C under reduced pressure to dissolve uniformly and dehydrate. Then, the pressure inside the autoclave and the condensation device was reduced to 5 kPa. 440 parts of PO were continuously added to the liquid phase through the raw material supply line while controlling the reaction temperature to be kept at 110 ° C. A refrigerant at -30 ° C was circulated to condense and recover PO in the condensation device. Then, after aging at 130 ° C for 4 hours, 0.7 parts of potassium hydroxide was added, and the mixture was stirred at 130 ° C under reduced pressure to dissolve uniformly and dehydrate. The temperature was then raised and heated at 160°C for 40 hours under a nitrogen atmosphere to rearrange the allyl group of the allyl-containing compound generated by a side reaction during the PO addition reaction to a propenyl group. After cooling to 90°C, 6 parts of synthetic silicate [Kyowa Chemical Industry Co., Ltd.'s "Kyoward 600 (registered trademark)] and 8 parts of water were added and mixed for 60 minutes, and the adsorbent was removed by filtration. Next, 0.02 parts of TPB was charged, stirring was started, and the pressure inside the autoclave and condensation equipment was reduced to 5 kPa. 10.2 parts of PO were continuously added to the liquid phase through the raw material supply line over 12 hours while controlling the reaction temperature to be kept at 75°C. A refrigerant at -30°C was circulated to condense and recover PO in the condensation equipment. After aging for 4 hours at 70°C, 0.2 parts of phosphoric acid and 21 parts of water were added to adjust the pH to 4, and the mixture was heated at 150°C for 5 hours under a nitrogen atmosphere to hydrolyze the propenyl group and convert it to a hydroxyl group. The mixture was cooled to 120°C, and the pressure was kept at 5 kPa while steam was introduced, and water and by-product low boiling point compounds were distilled off under reduced pressure. The mixture was heated to 140°C, and water was distilled off under reduced pressure. The mixture was then cooled to 90°C, and 6 parts of a hydrotalcite-based adsorbent [Kyowa Chemical Industry Co., Ltd.'s "Kyoward 1000 (registered trademark)] was added and mixed for 30 minutes, after which the adsorbent was removed by filtration to obtain polyoxyalkylene polyol (a3-8). The hydroxyl value of (a3-8) was 27.9 mgKOH / g, the viscosity was 1.0 Pa·s / 25°C, the primary content rate was 41%, and the degree of unsaturation was 0.008 meq / g.

[0123] [Production of urethane adhesive base] <Example 1> In a four-neck flask equipped with a stirring rod and a thermometer, 1 part of polyester polyol (a1-1), 59 parts of polytetramethylene ether glycol (a2-1), and 40 parts of polyoxyalkylene polyol (a3-1) obtained in Production Example 1 were added, and the mixture was stirred under reduced pressure at 100°C for dehydration. After cooling to 50°C under a nitrogen atmosphere, 69 parts of ethyl acetate as a solvent, 0.05 parts of diethyl malonate as a gelling inhibitor, and 3.6 parts of HDI were added in that order. The mixture was stirred to make it uniform, and 0.02 parts of a bismuth compound ["Neostan U-600 (registered trademark)" manufactured by Nitto Kasei Co., Ltd.] was added as a catalyst. The mixture was heated to 76°C under a nitrogen atmosphere and reacted for 5 hours to obtain a main agent (S-1) containing a urethane prepolymer (P-1) having a hydroxyl group. The weight average molecular weight of (P-1) was 78,000, the hydroxyl value was 12.8 mgKOH / g, the weight ratio of ester groups was 0.35% by weight, and the aromatic ring concentration was 0.0% by weight.

[0124] <Example 2> Into a four-neck flask similar to that of Example 1, 10 parts of polyester polyol (a1-1), 58 parts of polytetramethylene ether glycol (a2-1), and 32 parts of polyoxyalkylene polyol (a3-1) obtained in Production Example 1 were charged, and the mixture was dehydrated by stirring under reduced pressure at 100°C. After cooling to 50°C under a nitrogen atmosphere, 69 parts of ethyl acetate, 0.05 parts of diethyl malonate, and 3.9 parts of HDI were charged in that order. The mixture was stirred to make it uniform, and 0.02 parts of a bismuth compound was charged, and the mixture was heated to 76°C under a nitrogen atmosphere and reacted for 5 hours to obtain a main agent (S-2) containing a urethane prepolymer (P-2) having a hydroxyl group. The weight average molecular weight of (P-2) was 72,000, the hydroxyl value was 12.6 mgKOH / g, the weight ratio of ester groups was 3.49% by weight, and the aromatic ring concentration was 0.0% by weight.

[0125] <Example 3> Into a four-neck flask similar to that of Example 1, 5 parts of polyester polyol (a1-2), 30 parts of polytetramethylene ether glycol (a2-1), and 65 parts of polyoxyalkylene polyol (a3-3) obtained in Production Example 3 were charged, and the mixture was dehydrated by stirring under reduced pressure at 100°C. After cooling to 50°C under a nitrogen atmosphere, 69 parts of ethyl acetate, 0.05 parts of diethyl malonate, and 3.4 parts of HDI were charged in that order. The mixture was stirred to make it uniform, and 0.02 parts of a bismuth compound was charged, and the mixture was heated to 76°C under a nitrogen atmosphere and reacted for 5 hours to obtain a main agent (S-3) containing a urethane prepolymer (P-3) having a hydroxyl group. The weight average molecular weight of (P-3) was 152,000, the hydroxyl value was 14.3 mgKOH / g, the weight ratio of ester groups was 1.79% by weight, and the aromatic ring concentration was 0.0% by weight.

[0126] <Example 4> Into a four-neck flask similar to that of Example 1, 3 parts of polyester polyol (a1-3), 57 parts of polytetramethylene ether glycol (a2-2), and 40 parts of polyoxyalkylene polyol (a3-2) obtained in Production Example 2 were charged, and the mixture was dehydrated by stirring under reduced pressure at 100°C. After cooling to 50°C under a nitrogen atmosphere, 70 parts of ethyl acetate, 0.05 parts of diethyl malonate, and 4.9 parts of IPDI ["Desmodur I" manufactured by Sumika Covestro Urethane Co., Ltd.] were charged in order. The mixture was stirred to make it uniform, and 0.02 parts of a bismuth compound was charged, and the temperature was raised to 76°C under a nitrogen atmosphere and reacted for 5 hours to obtain a main agent (S-4) containing a urethane prepolymer (P-4) having a hydroxyl group. The weight average molecular weight of (P-4) was 86,000, the hydroxyl value was 12.3 mgKOH / g, the weight ratio of the ester group was 0.85% by weight, and the aromatic ring concentration was 0.0% by weight.

[0127] <Example 5> 20 parts of polyester polyol (a1-2), 50 parts of polytetramethylene ether glycol (a2-1), and 30 parts of polyoxyalkylene polyol (a3-3) obtained in Production Example 3 were added to a four-neck flask similar to that of Example 1, and the mixture was dehydrated by stirring under reduced pressure at 100°C. After cooling to 50°C under a nitrogen atmosphere, 70 parts of ethyl acetate, 0.05 parts of diethyl malonate, and 4.8 parts of IPDI were added in that order. The mixture was stirred to make it uniform, and 0.02 parts of a bismuth compound was added. The mixture was heated to 76°C under a nitrogen atmosphere and reacted for 5 hours to obtain a base material (S-5) containing a urethane prepolymer (P-5) having a hydroxyl group. The weight average molecular weight of (P-5) was 103,000, the hydroxyl value was 13.2 mgKOH / g, the weight ratio of ester groups was 7.07% by weight, and the aromatic ring concentration was 0.0% by weight.

[0128] <Example 6> Into a four-neck flask similar to that of Example 1, 10 parts of polyester polyol (a1-1), 50 parts of polytetramethylene ether glycol (a2-1), and 40 parts of polyoxyalkylene polyol (a3-1) obtained in Production Example 1 were charged, and the mixture was dehydrated by stirring under reduced pressure at 100°C. After cooling to 50°C under a nitrogen atmosphere, 69 parts of ethyl acetate, 0.05 parts of diethyl malonate, and 3.8 parts of HDI were charged in that order. The mixture was stirred to make it uniform, and 0.02 parts of a bismuth compound was charged, and the mixture was heated to 76°C under a nitrogen atmosphere and reacted for 5 hours to obtain a base material (S-6) containing a urethane prepolymer (P-6) having a hydroxyl group. The weight average molecular weight of (P-6) was 121,000, the hydroxyl value was 13.4 mgKOH / g, the weight ratio of ester groups was 3.50% by weight, and the aromatic ring concentration was 0.0% by weight.

[0129] <Example 7> Into a four-neck flask similar to that of Example 1, 15 parts of polyester polyol (a1-2), 45 parts of polytetramethylene ether glycol (a2-1), and 40 parts of polyoxyalkylene polyol (a3-3) obtained in Production Example 3 were charged, and the mixture was dehydrated by stirring under reduced pressure at 100°C. After cooling to 50°C under a nitrogen atmosphere, 70 parts of ethyl acetate, 0.05 parts of diethyl malonate, and 4.9 parts of IPDI were charged in that order. The mixture was stirred to make it uniform, and 0.02 parts of a bismuth compound was charged, and the mixture was heated to 76°C under a nitrogen atmosphere and reacted for 5 hours to obtain a base material (S-7) containing a urethane prepolymer (P-7) having a hydroxyl group. The weight average molecular weight of (P-7) was 98,000, the hydroxyl value was 12.4 mgKOH / g, the weight ratio of ester groups was 5.30% by weight, and the aromatic ring concentration was 0.0% by weight.

[0130] <Example 8> Into a four-neck flask similar to that of Example 1, 3 parts of polyester polyol (a1-3), 42 parts of polytetramethylene ether glycol (a2-2), and 55 parts of polyoxyalkylene polyol (a3-2) obtained in Production Example 2 were charged, and the mixture was dehydrated by stirring under reduced pressure at 100°C. After cooling to 50°C under a nitrogen atmosphere, 70 parts of ethyl acetate, 0.05 parts of diethyl malonate, and 4.9 parts of IPDI were charged in that order. The mixture was stirred to make it uniform, and 0.02 parts of a bismuth compound was charged, and the mixture was heated to 76°C under a nitrogen atmosphere and reacted for 5 hours to obtain a base material (S-8) containing a urethane prepolymer (P-8) having a hydroxyl group. The weight average molecular weight of (P-8) was 109,000, the hydroxyl value was 12.8 mgKOH / g, the weight ratio of the ester group was 0.85% by weight, and the aromatic ring concentration was 0.0% by weight.

[0131] <Example 9> Into a four-neck flask similar to that of Example 1, 5 parts of polyester polyol (a1-1), 50 parts of polytetramethylene ether glycol (a2-1), 35 parts of polyoxyalkylene polyol (a3-1) obtained in Production Example 1, and 10 parts of polyether polyol (a42-1) other than (a2) and (a3) ​​were added, and the mixture was dehydrated by stirring under reduced pressure at 100°C. After cooling to 50°C under a nitrogen atmosphere, 70 parts of ethyl acetate, 0.05 parts of diethyl malonate, and 4.6 parts of HDI were added in that order. The mixture was stirred to make it uniform, and 0.02 parts of a bismuth compound was added, and the mixture was heated to 76°C under a nitrogen atmosphere and reacted for 5 hours to obtain a base material (S-9) containing a urethane prepolymer (P-9) having a hydroxyl group. The weight average molecular weight of (P-9) was 113,000, the hydroxyl value was 14.0 mgKOH / g, the weight ratio of ester groups was 1.73% by weight, and the aromatic ring concentration was 1.3% by weight.

[0132] <Example 10> Into a four-neck flask similar to that of Example 1, 10 parts of polyester polyol (a1-1), 50 parts of polytetramethylene ether glycol (a2-1), and 40 parts of polyoxyalkylene polyol (a3-8) obtained in Production Example 8 were charged, and the mixture was dehydrated by stirring under reduced pressure at 100°C. After cooling to 50°C under a nitrogen atmosphere, 70 parts of ethyl acetate, 0.05 parts of diethyl malonate, and 4.5 parts of IPDI were charged in that order. The mixture was stirred to make it uniform, and 0.02 parts of a bismuth compound was charged, and the mixture was heated to 76°C under a nitrogen atmosphere and reacted for 5 hours to obtain a base material (S-10) containing a urethane prepolymer (P-10) having a hydroxyl group. The weight average molecular weight of (P-10) was 144,000, the hydroxyl value was 12.9 mgKOH / g, the weight ratio of ester groups was 3.47% by weight, and the aromatic ring concentration was 0.0% by weight.

[0133] <Example 11> Into a four-neck flask similar to that of Example 1, 20 parts of polyester polyol (a1-2), 50 parts of polytetramethylene ether glycol (a2-1), 3 parts of polyoxyalkylene polyol (a3-3) obtained in Production Example 3, and 27 parts of polyoxyalkylene polyol (a3-8) obtained in Production Example 8 were added, and the mixture was stirred under reduced pressure at 100°C for dehydration. After cooling to 50°C under a nitrogen atmosphere, 70 parts of ethyl acetate, 0.05 parts of diethyl malonate, and 4.3 parts of IPDI were added in that order. The mixture was stirred to make it uniform, and 0.02 parts of a bismuth compound was added, and the mixture was heated to 76°C under a nitrogen atmosphere and reacted for 5 hours to obtain a base material (S-11) containing a urethane prepolymer (P-11) having a hydroxyl group. The weight average molecular weight of (P-11) was 101,000, the hydroxyl value was 13.0 mgKOH / g, the weight ratio of ester groups was 7.11% by weight, and the aromatic ring concentration was 0.0% by weight.

[0134] <Comparative Example 1> Into a four-neck flask similar to that of Example 1, 15 parts of polyester polyol (a1'-1), 30 parts of polytetramethylene ether glycol (a2-2), and 55 parts of polyoxyalkylene polyol (a3-5) obtained in Production Example 5 were charged, and the mixture was dehydrated by stirring under reduced pressure at 100°C. After cooling to 50°C under a nitrogen atmosphere, 71 parts of ethyl acetate, 0.05 parts of diethyl malonate, and 6.5 parts of IPDI were charged in that order. The mixture was stirred to make it uniform, and 0.02 parts of a bismuth compound was charged, and the mixture was heated to 76°C under a nitrogen atmosphere and reacted for 5 hours to obtain a main agent (S'-1) containing a urethane prepolymer (P'-1) having a hydroxyl group. The weight average molecular weight of (P'-1) was 71,000, the hydroxyl value was 14.6 mgKOH / g, the weight ratio of ester groups was 5.97% by weight, and the aromatic ring concentration was 0.0% by weight.

[0135] <Comparative Example 2> Into a four-neck flask similar to that of Example 1, 2 parts of polyester polyol (a1-3), 49 parts of polyoxyalkylene polyol (a3-7), and 49 parts of polyoxyalkylene polyol (a3-6) obtained in Production Example 6 were added, and the mixture was dehydrated by stirring under reduced pressure at 100°C. After cooling to 50°C under a nitrogen atmosphere, 69 parts of ethyl acetate, 0.05 parts of diethyl malonate, and 4.2 parts of IPDI were added in that order. The mixture was stirred to make it uniform, and 0.02 parts of a bismuth compound was added, and the mixture was heated to 76°C under a nitrogen atmosphere and reacted for 5 hours to obtain a main agent (S'-2) containing a urethane prepolymer (P'-2) having a hydroxyl group. The weight average molecular weight of (P'-2) was 128,000, the hydroxyl value was 12.1 mgKOH / g, the weight ratio of ester groups was 0.57% by weight, and the aromatic ring concentration was 0.0% by weight.

[0136] <Comparative Example 3> Into a four-neck flask similar to that of Example 1, 60 parts of polytetramethylene ether glycol (a2-1) and 40 parts of polyoxyalkylene polyol (a3-5) obtained in Production Example 5 were added, and the mixture was dehydrated by stirring under reduced pressure at 100°C. After cooling to 50°C under a nitrogen atmosphere, 70 parts of ethyl acetate, 0.05 parts of diethyl malonate, and 4.4 parts of HDI were added in that order. The mixture was stirred to make it uniform, and 0.02 parts of a bismuth compound was added, and the mixture was heated to 76°C under a nitrogen atmosphere and reacted for 5 hours to obtain a main agent (S'-3) containing a urethane prepolymer (P'-3) having a hydroxyl group. The weight average molecular weight of (P'-3) was 76,000, the hydroxyl value was 15.4 mgKOH / g, the weight ratio of ester groups was 0.00% by weight, and the aromatic ring concentration was 0.0% by weight.

[0137] <Comparative Example 4> Into a four-neck flask similar to that of Example 1, 8 parts of polyester polyol (a1-2), 42 parts of polytetramethylene ether glycol (a2-2), and 50 parts of polyoxyalkylene polyol (a3-4) obtained in Production Example 4 were charged, and the mixture was dehydrated by stirring under reduced pressure at 100°C. After cooling to 50°C under a nitrogen atmosphere, 69 parts of ethyl acetate, 0.05 parts of diethyl malonate, and 3.3 parts of HDI were charged in that order. The mixture was stirred to make it uniform, and 0.02 parts of a bismuth compound was charged, and the mixture was heated to 76°C under a nitrogen atmosphere and reacted for 5 hours to obtain a main agent (S'-4) containing a urethane prepolymer (P'-4) having a hydroxyl group. The weight average molecular weight of (P'-4) was 98,000, the hydroxyl value was 11.5 mgKOH / g, the weight ratio of ester groups was 2.87% by weight, and the aromatic ring concentration was 0.0% by weight.

[0138] Table 1 shows a list of the raw materials and their amounts used in Examples 1 to 11 and Comparative Examples 1 to 4, as well as the properties of the resulting urethane prepolymers and base resins.

[0139] [Table 1]

[0140] In Table 1, the components are as follows. Polyester polyol (a1-1): Polycondensation product of 3-methyl-1,5-pentanediol and adipic acid [Kuraray Polyol P-2010 manufactured by Kuraray Co., Ltd.: Primary content = 100%, hydroxyl value = 56.5 mgKOH / g] Polyester polyol (a1-2): Polycondensation product of 3-methyl-1,5-pentanediol and adipic acid [Kuraray Polyol P-3010 manufactured by Kuraray Co., Ltd.: Primary content = 100%, hydroxyl value = 37.6 mgKOH / g] Polyester polyol (a1-3): Polycondensation product of 3-methyl-1,5-pentanediol and adipic acid [Kuraray Polyol P-510 manufactured by Kuraray Co., Ltd.: Primary content = 100%, hydroxyl value = 222 mgKOH / g] Polyester polyol (a1'-1): Polybutylene adipate ["Sun-Estar 4620 (registered trademark)" manufactured by Sanyo Chemical Industries, Ltd.: primary polyol content = 100%, hydroxyl value = 55.6 mg KOH / g] Polytetramethylene ether glycol (a2-1): [Mitsubishi Chemical Corporation "PTMG3000": primary content = 100%, hydroxyl value = 38.5 mgKOH / g] Polytetramethylene ether glycol (a2-2): [Mitsubishi Chemical Corporation "PTMG4000": primary content = 100%, hydroxyl value = 30.0 mgKOH / g] Polyoxyalkylene polyol (a3-1): Polyoxyalkylene polyol obtained in Production Example 1 Polyoxyalkylene polyol (a3-2): Polyoxyalkylene polyol obtained in Production Example 2 Polyoxyalkylene polyol (a3-3): Polyoxyalkylene polyol obtained in Production Example 3 Polyoxyalkylene polyol (a3-4): Polyoxyalkylene polyol obtained in Production Example 4 Polyoxyalkylene polyol (a3-5): Polyoxyalkylene polyol obtained in Production Example 5 Polyoxyalkylene polyol (a3-6): Polyoxyalkylene polyol obtained in Production Example 6 Polyoxyalkylene polyol (a3-7): Polyoxyalkylene polyol obtained in Production Example 7 Polyoxyalkylene polyol (a3-8): Polyoxyalkylene polyol obtained in Production Example 8 Polyether polyol (a42-1) other than (a2) and (a3): ethylene oxide adduct of bisphenol A ["Newpol BPE-180 (registered trademark)" manufactured by Sanyo Chemical Industries, Ltd.: primary content = 100%, hydroxyl value = 108 mg KOH / g, aromatic ring concentration = 14 wt%] Bismuth compound: ["Neostan U-600 (registered trademark)" manufactured by Nitto Kasei Co., Ltd.]

[0141] <Examples 12 to 28 and Comparative Examples 5 to 9> Each of the base materials for urethane adhesives (S-1) to (S-11), (S'-1) to (S'-4), polytetramethylene ether glycol (a2-1), curing agent {crosslinking agent (C-1): HDI-based isocyanurate type polyisocyanate [Asahi Kasei Corporation's "Duranate TFD-90B (registered trademark)"], crosslinking agent (C-2): HDI-based isocyanurate type polyisocyanate [Asahi Kasei Corporation's "Duranate TKA-100 (registered trademark)"], crosslinking agent (C-3): HDI-based burette type polyisocyanate [Asahi Kasei Corporation's "Duranate 24A-100 (registered trademark)"], or crosslinking agent (C-4): HDI-based adduct type polyisocyanate [Asahi Kasei Corporation's "Duranate AE700-100 (registered trademark)"]}, zinc catalyst [Borchi A catalyst [dibutyltin dilaurate] or a tin catalyst [dibutyltin dilaurate], acetylacetone as a cure retarder, and ethyl acetate as a solvent were mixed in the amounts shown in Table 2 and centrifuged to degas the mixture to obtain an adhesive solution. The mixture was applied to a 50 μm thick highly adhesive polyester film using an applicator so that the film thickness after drying would be 50 μm. The mixture was dried at 120°C for 3 minutes, and a release film was attached. The mixture was then aged at 50°C for 3 days to obtain adhesive sheets (T-1) to (T-17) and (T'-1) to (T'-5). The obtained adhesive sheets were evaluated by the following methods, and the results are shown in Table 2.

[0142] [Table 2]

[0143] (1) Evaluation method for light peelability Each adhesive sheet was cut to a size of 100 mm x 25 mm, the release film was peeled off, and the sheet was pressed onto a glass plate using a roller weighing 2 kg. Using a tensile tester, the 180° peel strength (adhesive strength) was measured at 23°C and a pulling speed of 300 mm / min. Measurements were performed on three samples, and the average value was used for evaluation. When used as a surface protection film, it is required that the film does not peel off from the adherend and that it can be easily peeled off from the adherend, so that the adhesive strength is preferably 0.01 N / 25 mm or more and less than 0.05 N / 25 mm.

[0144] (2) Transparency assessment method Each adhesive sheet was cut to a size of 100 mm x 25 mm, the release film was removed, and the sheet was pressed onto a glass plate using a roller weighing 2 kg to prepare a sample for evaluation. The haze value was measured using a spectroscopic colorimeter and haze meter "COH7700" manufactured by Nippon Denshoku Industries Co., Ltd. Measurements were performed on three samples, and the average value was used for evaluation. When used as a surface protection film, the haze value is preferably less than 2.0%, as this reduces visibility and makes it difficult to detect foreign matter such as dust that has gotten in.

[0145] (3) Evaluation method for cutting ability The release film was removed from each adhesive sheet, and the adhesive surface was quickly cut with the blade of a cutter. The cut surface was visually observed through a magnifying glass, and the cuttability was evaluated according to the following criteria. It is preferable that no cutting chips are generated during processing, as cutting chips contaminate the adherend and reduce its performance. <Evaluation criteria> ◯: The cut surface is smooth and no cutting chips are generated. △: The cut surface is not smooth, but no cutting chips are generated. ×: The cut surface is not smooth and chips are generated.

[0146] (4) Method for evaluating conformability to substrate Each adhesive sheet was cut to a size of 100 mm x 25 mm, the release film was removed, and the adhesive surface was attached horizontally to the side of a glass tube bottle with a diameter of 35 mm. After leaving it at 25°C for 24 hours, the length of the part that peeled off from the glass tube bottle was measured. Measurements were taken at both ends, and the average length was used for evaluation. Since it is preferable for the adhesive sheet to remain attached to the adherend without peeling off even if the adherend is a curved surface, it is preferable for the average length of the peeled part to be 1 cm or less. [Industrial Applicability]

[0147] The base agent for a two-component curing urethane adhesive of the present invention and the two-component curing urethane adhesive using the same are extremely useful as they can be used in a wide range of applications, such as protecting optical components in the production process of image display devices such as polarizing plates, and bonding optical components together.

Claims

1. A two-component curing urethane adhesive base material containing a urethane prepolymer (P) having a hydroxyl group, the urethane prepolymer (P) is a urethane prepolymer obtained by reacting a polyol component (A) containing a polyester polyol (a1), a polytetramethylene ether glycol (a2), and a polyoxyalkylene polyol (a3) ​​having a hydroxypropyl group at a molecular end with an organic polyisocyanate component (B); The polyester polyol (a1) is a reaction product of a polyol component (X) containing a diol (x1) having an alkyl group and a polycarboxylic acid component (Y), The polyoxyalkylene polyol (a3) ​​has a degree of unsaturation of 0.003 to 0.009 meq / g.

2. The base for a two-component curing urethane adhesive according to claim 1, wherein the content of the polyester polyol (a1) is 1 to 20% by weight based on the weight of the polyol component (A).

3. The base for a two-component curing urethane adhesive according to claim 1, wherein the content of the polytetramethylene ether glycol (a2) is 30 to 60% by weight based on the weight of the polyol component (A).

4. 2. The base for a two-component curing urethane adhesive according to claim 1, wherein the weight ratio of the ester group in the urethane prepolymer (P) is 0.3 to 10% by weight.

5. The base agent for a two-component curing urethane adhesive according to claim 1, wherein the polyoxyalkylene polyol (a3) ​​having a hydroxypropyl group at the molecular end has an average number of functional groups per molecule of 2.1 to 3.

0.

6. The base for a two-component curing urethane pressure-sensitive adhesive according to claim 1, wherein the polyoxyalkylene polyol (a3) ​​having a hydroxypropyl group at its molecular terminal has a primary hydroxyl group content of 40% or more.

7. The base for a two-component curing urethane adhesive according to claim 1, wherein the urethane prepolymer (P) has a hydroxyl value of 12 to 14 mgKOH / g.

8. The base agent for the two-component curing urethane adhesive according to claim 1 , which contains a bismuth compound.

9. The base for a two-component curing urethane adhesive according to claim 1, wherein the concentration of aromatic rings in the urethane prepolymer (P) is 5% by weight or less.

10. The base for a two-component curing urethane adhesive according to claim 1, wherein a weight ratio (a3 / a2) of the polyoxyalkylene polyol (a3) ​​to the polytetramethylene ether glycol (a2) in the polyol component (A) is 0.3 to 2.4.

Citation Information

Patent Citations

  • Polyurethane pressure-sensitive adhesive composition, and pressure-sensitive adhesive sheet and surface-protecting film

    JP2006182795A

  • Adhesive and adhesive sheet

    JP2018062595A

  • Surface protective film

    JP2022098051A